Understanding ecosystem responses to recurrent marine heatwaves - Emily Lester; Stanley Mastrantonis; Sharyn M. Hickey; Anna Lafratta; Jessica A. Benthuysen; Eben Afrifa-Yamoah; Arani Chandrapavan; Martial Depczynski; Richard D. Evans; David V. Fairclough; Christopher J. Fulton; Marthe Monique Gagnon; et al. (Biological Conservation, 2026)

Multiphase coupling of phosphorus and organic matter across water–particle interaction in aquaculture ponds - Xiangcheng Kong; Sarah E. Rice; Harlow S. Kramer-Dew; Andrew R. Zimmerman; Christopher J. Martyniuk; Young Gu Her; Eban Bean; Jonathan D. Judy; Yuncong Li; Alan E. Wilson; Dengjun Wang (Journal of Hazardous Materials, 2026)

Quantitative assessment of knowledge gaps and research priorities for understanding and managing population irruptions of crown-of-thorns starfish (Acanthaster cf. solaris) on Australia’s Great Barrier Reef - Morgan S. Pratchett; Peter C. Doll; Christopher Cvitanovic; Shaun K. Wilson; Russell C. Babcock; Yves-Marie Bozec; Deborah Burn; Maria Byrne; Carolina Castro-Sanguino; Carla C. M. Chen; Scott A. Condie; Zara-Louise Cowan; et al. (Coral Reefs, 2026)
Despite extensive research on the western Pacific crown-of-thorns starfish (CoTS; Acanthaster cf. solaris ), especially from Australia’s Great Barrier Reef (GBR), there are persistent knowledge gaps that constrain understanding and management. Given renewed population irruptions of CoTS on the GBR, alongside escalating climate impacts and direct anthropogenic pressures, a quantitative assessment of knowledge gaps was undertaken to identify research priorities and guide future efforts. In this study, 27 experts independently scored 206 research questions across seven Themes and 39 topics, based on four different criteria ( Knowledge gap , Feasibility , Urgency , and Applicability ). These questions were ultimately rationalized into 170 distinct questions, with scores aggregated across merged questions. Management was the highest scoring Theme for Urgency , Applicability , and overall. All but six of the 20 top-ranked questions were from the Management Theme and mainly related to Culling and/ or Monitoring. Most questions (158 out of 170) also scored highly for Feasibility , suggesting that there are existing methods and technical capability available to advance the extensive and diverse range of research questions that were posed, if resources were made available. This quantitative assessment provides guidance on the prioritization of potential research that could improve management of CoTS populations to improve coral protection outcomes on the GBR. This study also suggests that there are limited constraints to undertaking necessary research to address many of the persistent knowledge gaps relating to CoTS.

Smooth Gradients or Defined Fronts: Characterizing Within-Marsh Spatial Variability of CO2 Fluxes - Lena K. Champlin; Emily Wilson; Kenneth B. Raposa; Jason S. Goldstein; Ashley Hamilton; Jason S. Krumholz; Christopher R. Peter; Megan C. Tyrrell; Jamie M. P. Vaudrey; Robinson W. Fulweiler (Estuaries and Coasts, 2026)

Using Organoids to Unlock the Potential of Human Torpor for Spaceflight - Jonathan Diaz; Joshua T. Maxwell; Paul F. Wilson; Alan Jacobson; Anthony Atala; Graça Almeida-Porada; Christopher D. Porada (Current Stem Cell Reports, 2026)
Purpose of Review This paper reviews the current understanding of the potential for humans to enter a state of torpor/hibernation, and discusses the possibility of inducing torpor in astronauts for long-duration space travel, including some of the physiological, technological, and ethical considerations associated with its implementation. By exploring means to induce torpor in various human organoid systems, we hope such research can provides insights to comprehensive solutions to overcome some of the major hurdles that limit the potential for human to enter a state of torpor during long-duration deep-space missions, and contribute to the ongoing efforts to make such missions more feasible and safer for astronauts. Recent Findings On future deep space missions such as NASA’s planned missions to the Moon, Mars, and near-Earth asteroids, astronauts will be continuously exposed to environments that are radically different from those on Earth, each presenting multiple logistical and physiological challenges. Beyond the well-documented physiological effects of microgravity, space travelers will encounter a complex radiation environment that may contribute to significant short- and long-term adverse effects on human physiology and increase the risk of cancer and other diseases. Besides these physical challenges, life support systems must also be designed to mitigate psychological impacts of long-term isolation and confinement – all of which collectively pose formidable engineering problems. Hibernation/torpor is a state of prolonged inactivity and metabolic depression used by a wide variety of mammals to survive periods of cold temperatures and food scarcity, including some primates and perhaps even an extinct early line of hominins that lived nearly half a million years ago. Since modern humans share common ancestry with these hominins and hibernating primates, it is likely the human genome encodes the necessary genetic information to hibernate, or at least enter the similar, more transient state of torpor. The reduced body activity, lowered metabolism, and decreased energy requirements that characterize torpor suggest that developing means of inducing such a state in astronauts could address these challenges, including providing a degree of radioprotection. Summary This review explores the potential application of human torpor as a countermeasure to address the many challenges posed by long-duration spaceflight beyond low-Earth orbit (LEO), discusses various natural hibernating model systems for studying means of inducing a torpor-like state in humans, and highlights the vast potential of using human organoids to test and validate mechanisms that govern induction and maintenance of torpor to identify the means to one day safely induce this state in astronauts to provide additional protection from the myriad stressors of spaceflight.

Anxiety disorders alter cognitive-motor integration during visuomotor adaptation and retention - Leo Barzi; Matt Wilson; Christopher M. Hill (Experimental Brain Research, 2026)
Anxiety disorders are associated with prefrontal dysfunction, yet their impact on neural mechanisms underlying skilled motor learning remains poorly understood. We examined movement-readiness potentials (MRPs) using electroencephalography during a visuomotor adaptation task in 31 young adults (13 with clinically diagnosed anxiety disorders, 18 controls). MRPs were analyzed across three temporal components: early motor preparation (− 1500 to − 500 ms), late motor preparation (− 500 to − 100 ms), and movement execution (− 100 to + 100 ms). Individuals with anxiety disorders showed significantly reduced MRP amplitudes during late motor preparation ( p = 0.033) and movement execution ( p = 0.047) compared to controls, while early motor preparation remained intact. Despite these neural alterations, both groups demonstrated equivalent behavioral performance, with similar learning and retention of a visuomotor rotation task. Anxiety disorders selectively disrupt late-stage cognitive-motor integration processes during movement preparation and execution. The dissociation between impaired neural activity and preserved behavioral performance suggests compensatory mechanisms that maintain motor learning despite underlying neural inefficiencies. These findings reveal that anxiety affects integrated systems of cognition and action, providing new insights into their functional neurophysiological impact.

Dynamic Phenology of Canopy-Forming Macroalgal Forests within a Tropical Seascape - Shaun K. Wilson; Christopher J. Fulton; Martial Depczynski; Ben Radford; Thomas H. Holmes; Matthew Birt; Cal Faubel; Marjetta L. Puotinen; Mae Noble; Richard D. Evans; Molly Moustaka; Paul Tinkler; et al. (Ecosystems, 2026)
Biomass dynamics of primary producers provide a basis for assessing their capacity to capture carbon and mitigate excess greenhouse gases. Here, we estimate inter-annual and seasonal biomass cycles in canopy-forming Sargassaceae at 19 sites spanning ~ 200 km of the Ningaloo World Heritage Area over 11 consecutive years. Our global average summer estimate of 1.53 kg wet wt m −2 equates to 4.1–9.4 Gg of standing macroalgal carbon (14.9–34.6 Gg CO 2 ) across 38,300 ha of all macroalgae habitats. Biomass estimates did not differ significantly among years but varied by an order of magnitude among sites. Accumulation typically occurred during the spring, followed by a loss of 42–94 Gg wet weight, or 1.4–3.3 Gg organic carbon (5.3–12.0 Gg CO 2 ) fixed in macroalgal habitats during autumn. Seasonal patterns of biomass accumulation and release were, however, spatially and temporally variable, some sites accumulating biomass in autumn and releasing it during the following spring. Spring biomass accumulation was reduced by herbivorous urchins, whilst the extent of macroalgae biomass change in the autumn was directly correlated with sea temperature and standing biomass the previous summer. These findings imply canopy-forming macroalgae provide a regular injection of biomass into the surrounding ecosystems, which support productivity of surrounding habitats and is a potential source of organic carbon for burial in carbon sinks throughout the year. Modelling that seeks to link macroalgae sources with sinks therefore requires a spatially explicit understanding of when seasonal senescence of canopy-forming macroalgae occurs, inter-site variability and the environmental conditions that govern this phenology.

Uptake and Elimination of 7 Selected PFAS in Eisenia Fetida Exposed in Artificial Soil - Jonathan D. Judy; Caleb Gravesen; P. Christopher Wilson; Ann Wilkie; Jennifer Sarchapone; Francisca Hinz; Xinya Yang; Nevaeh Renwick (Bulletin of Environmental Contamination and Toxicology, 2026)

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

SNAPSHOT USA 2024: Year 6 of the Coordinated National Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Daniel J. Herrera; Camilla Price; Phuong‐Thao Nguyen‐Nu; Katrina Adamczyk; Peter D. Alexander; David Allen; Jesse M. Alston; Diego F. Alvarado‐Serrano; et al. (Global Ecology and Biogeography, 2026)
Motivation SNAPSHOT USA is an annual, multi‐contributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2024 contains 377,427 records of camera trap image sequence data and 3127 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in 49 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1 August and 19 December in 2024. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2024 comprises two .csv files. The original data can be found within the SNAPSHOT USA 2024 project on the Wildlife Insights platform.

Dietary administration of α-terpineol to Sprague-Dawley rats for 90 days - Michel Aubanel; Christopher Choi; Jan Demyttenaere; Maodo Malick Diop; Sylvain Etter; Alexandra Blanchard; Christie L. Harman; Mihoko Koyanagi; Gerhard Krammer; Gregory Ladics; Severin Müller; George Pugh; et al. (Regulatory Toxicology and Pharmacology, 2026)

Miocene high-pressure metamorphism of garnet-bearing amphibolites in the Cona area, southern Tibet: Insights into the tectonic evolution of the Higher Himalaya - Khizar Hayat; Laixi Tong; Zhao Liu; Christopher J.L. Wilson; Xiaohan Liu; Kexin Wu; Xinyue Han (Journal of Asian Earth Sciences, 2026)

Calibrating a regional growth and yield model for statewide forest carbon assessment in four common forest types in Minnesota, USA - Matthew B. Russell; John M. Zobel; David C. Wilson; Marcella A. Windmuller-Campione; Tyler S. Gifford; John DuPlissis; Christopher B. Edgar (Forest Policy and Economics, 2026)

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

Vulnerability of marine megafauna to global at‐sea anthropogenic threats - Michelle VanCompernolle; Juliet Morris; Hannah J. Calich; Jorge P. Rodríguez; Sarah A. Marley; Jessica R. Pearce; Briana Abrahms; Katya Abrantes; André S. Afonso; Alex Aguilar; Andrews Agyekumhene; Tomonari Akamatsu; et al. (Conservation Biology, 2026)
Marine megafauna species are affected by a wide range of anthropogenic threats. To evaluate the risk of such threats, species’ vulnerability to each threat must first be determined. We build on the existing threats classification scheme and ranking system of the International Union for Conservation of Nature (IUCN) Red List of Threatened Species by assessing the vulnerability of 256 marine megafauna species to 23 at‐sea threats. The threats we considered included individual fishing gear types, climate‐change‐related subthreats not previously assessed, and threats associated with coastal impacts and maritime disturbances. Our ratings resulted in 70 species having high vulnerability ( v > 0.778 out of 1) to at least 1 threat, primarily drifting longlines, temperature extremes, or fixed gear. These 3 threats were also considered to have the most severe effects (i.e., steepest population declines). Overall, temperature extremes and plastics and other solid waste were rated as affecting the largest proportion of populations. Penguins, pinnipeds, and polar bears had the highest vulnerability to temperature extremes. Bony fishes had the highest vulnerability to drifting longlines and plastics and other solid waste; pelagic cetaceans to 4 maritime disturbance threats; elasmobranchs to 5 fishing threats; and flying birds to drifting longlines and 2 maritime disturbance threats. Sirenians and turtles had the highest vulnerability to at least one threat from all 4 categories. Despite not necessarily having severe effects for most taxonomic groups, temperature extremes were rated among the top threats for all taxa except bony fishes. The vulnerability scores we provide are an important first step in estimating the risk of threats to marine megafauna. Importantly, they help differentiate scope from severity, which is key to identifying threats that should be prioritized for mitigation.

The Toxicology Investigators Consortium 2024 Annual Report - Kim Aldy; Shao Li; Mari Costantini; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; Michael Abesamis; Faiz Ahmed; Salman Ahsan; Peter Akpunonu; Adam Algren; et al. (Journal of Medical Toxicology, 2026)

Particle size-dependent partitioning of phosphorus in aquaculture pond and estuarine systems - Xiangcheng Kong; Chongyang Wang; Sarah E. Rice; Islam M. Radwan; Christopher J. Martyniuk; Alan E. Wilson; Dengjun Wang (Water Research, 2025)

Best practices for producing actionable knowledge to inform fisheries management and conservation - Cosette Arseneault-Deraps; Raegan Davis; M. E. Cole MacLeod; Erin Wilson; Ben Aubrey; Alyssa Goodenough; Jamie C. Madden; Kevin A. Adeli; Christopher Cvitanovic; Nathan Young; Julie M. Hinderer; Elizabeth A. Nyboer; et al. (Environmental Biology of Fishes, 2025)

Influence of pesticide application practices, pruning, and planting on contamination of nectar in container-grown lantana - Mia Cabrera; Sandra B. Wilson; P. Christopher Wilson; Vanesa Rostán; Edzard van Santen (Science of The Total Environment, 2025)

Late Quaternary inundation and desiccation of Megalake Chad traced in dust records from the Equatorial Atlantic Ocean - Anya J. Crocker; Christopher W. Kinsley; Amy M. Jewell; Paul S. Breeze; Nicholas A. Drake; David McGee; Charles S. Bristow; Katie Manning; Claudia Di Biagio; Paola Formenti; William R.C. Burton; Annie L. Murray; et al. (Quaternary Science Reviews, 2025)

Winter-Spring dynamics of dissolved organic carbon fluxes driven by precipitation in a North Carolina tidal marsh - Marie Cindy Lebrasse; Blake A. Schaeffer; DelWayne R. Bohnenstiehl; Christopher L. Osburn; Megan M. Coffer; Ruoying He; Peter J. Whitman; Wilson B. Salls; David D. Graybill (Estuarine, Coastal and Shelf Science, 2025)

Relation of wind direction and coal terminal activity patterns with air pollution burden in a community bordering a coal export terminal, Curtis Bay, Maryland, USA - Lauren N. Deanes; Bonita D. Salmerón; Matthew A. Aubourg; Laura E. Schmidt; Kristoffer Spicer; Caila Wagar; Gregory G. Sawtell; Carlos C. Sanchez-Gonzalez; David Jones; Angela Shaneyfelt; David H. Hagan; David McClosky; et al. (Air Quality, Atmosphere & Health, 2025)

The effect of early life thermal environment on morphology and growth of yellow perch ( Perca flavescens ) - Shamaila Fraz; W. Andrew Thompson; Milena S. Gallucci; Mariam Afridi; Mellissa Easwaramoorthy; Peyton Hartenstein; Lisa Laframboise; Ian Dworkin; Richard Manzon; Christopher M. Somers; Joanna Y. Wilson (Journal of Fish Biology, 2025)
Early life development in fishes is a period of high phenotypic plasticity. Water temperatures during embryogenesis can lead to alterations in growth and metabolic and morphological phenotypic variations. This study aimed to characterize the effects of temperature on the growth and morphology of yellow perch throughout early development, a species of significant ecological and economic importance in North America. Yellow perch ( Perca flavescens ) embryos were incubated at either constant temperature (12, 15, or 18°C) or under an ambient seasonal regime, where temperature increased throughout embryogenesis until it reached 18°C. All groups were gradually warmed at hatch until they reached 18°C, and morphology was assessed. Inverse relationships between temperature, length and yolk‐sac volume were found at the end of the embryonic period. Optimal embryonic growth was associated with the ambient seasonal regime. Fish reared at 15 or 18°C were larger and had higher growth rates when compared to those at 12°C following hatch. However, fish reared in cooler temperatures may possess more advantageous body shapes. Surprisingly, the ambient seasonal incubation had the lowest growth rate post‐hatch, even though this most closely mimicked natural incubation for this species. Because suitable larval morphology is related to survival and successful recruitment, these data suggest that yellow perch may be vulnerable to climate change and thermal pollution, although further work is needed to better predict the ecological implications of the phenotypes.

Behavioral differences of shelter dogs under fluorescent versus LED lighting - Jennifer Abrams; Kristiina Wilson; Janice Hegewald; Christopher Braun; Sarah-Elizabeth Byosiere (Applied Animal Behaviour Science, 2025)

Tracing Blue Carbon Flows Across Diverse Seascapes - Christopher J. Fulton; Diego R. Barneche; Kay Davis; Cal Faubel; Cecilia Pascelli; Julie Vercelloni; Shaun K. Wilson (Global Change Biology, 2025)
Plants occupying coastal ecosystems draw in carbon dioxide (CO 2 ) from the air and water around them during photosynthesis. A fraction of this CO 2 becomes fixed into plant biomass and can eventually contribute to the blue carbon pool—organic carbon (C org ) sequestered in slow‐turnover sinks. An important step in protecting and enhancing this natural carbon sequestration pathway is determining the relative contributions of different coastal plants to this blue carbon pool in durable sinks. We compiled a global dataset of coastal soil carbon measurements and used a Bayesian hierarchical meta‐regression model to explore the relative contribution of local (autochthonous) versus external (allochthonous) sources of C org in the soils beneath tidal saltmarsh, mangrove, and seagrass wetlands. We found most soil C org in coastal wetlands came from allochthonous sources, rather than the habitat‐forming plants. Managing climate‐resilient blue carbon seascapes, therefore, requires an awareness of this portfolio of contributors to soil carbon sequestration. However, study design aspects such as soil sampling depth, levels of sample replication, and the modeling approach used to trace C org can have pronounced effects on the estimated contributions of different carbon sources. We outline a roadmap for improving how we track the various drivers of soil carbon sequestration in diverse mosaics of coastal vegetation.

Miocene high-grade metamorphism of the metapelites in the Cona region, eastern Himalaya, and tectonic implications for Himalayan orogeny - Khizar Hayat; Laixi Tong; Xiaohan Liu; Christopher J.L. Wilson; Zhao Liu; Chao Li (Lithos, 2025)

An evaluation of the performance of a scroll machine in a reversible high-temperature heat pump - organic Rankine cycle system using R1233zd(E) as the working fluid - Rahul Velanparambil Ravindran; Donal Cotter; Christopher Wilson; Ming Jun Huang; Neil J Hewitt (International Journal of Refrigeration, 2025)

The wildlife nextdoor: Socioeconomics and race predict social media carnivore reports - Wilson C. Sherman; Christopher J. Schell; Christine E. Wilkinson (Science of The Total Environment, 2025)

Towards environmental justice: A framework and strategic approach for implementing community based participatory research in the earth and environmental sciences - Alexis M. Wilson; Emily Polk; Christopher B. Field; Scott Fendorf (Environmental Science & Policy, 2025)

Microscale to neighbourhood scale: Impact of shading on urban climate - Christopher Wilson; Jonathan K.P. Shonk; Sylvia I. Bohnenstengel; Athanasios Paschalis; Maarten van Reeuwijk (Building and Environment, 2025)

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

Bridging imaging-based in vitro methods from biomedical research to regulatory toxicology - Monica Piergiovanni; Milena Mennecozzi; Erio Barale-Thomas; Davide Danovi; Sebastian Dunst; David Egan; Aurora Fassi; Matthew Hartley; Philipp Kainz; Katharina Koch; Sylvia E. Le Dévédec; Iris Mangas; et al. (Archives of Toxicology, 2025)

Contrast enhancement after mechanical thrombectomy: clinical correlations and impact on outcomes - Farid Khasiyev; Wilson Rodriguez; Gunjanpreet Kaur; Irshad Allahverdiyev; Brian Miremadi; Kara Christopher; Guillermo Linares (Acta Neurologica Belgica, 2025)

Ontogeny of skeletogenesis in yellow perch and effects of early thermal environment on bone development - Shamaila Fraz; Sophie Klein; Milena Gallucci; Lisa Laframboise; Richard Manzon; Christopher M. Somers; Joanna Y. Wilson (Journal of Thermal Biology, 2025)

SNAPSHOT USA 2019–2023: The First Five Years of Data From a Coordinated Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Benjamin R. Goldstein; Christopher Pate; Paula Castiblanco; Maggie E. Abell; Jessie Adley; Briana Agenbroad; Adam A. Ahlers; Peter D. Alexander; et al. (Global Ecology and Biogeography, 2025)
Motivation SNAPSHOT USA is an annual, multicontributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2019–2023 contains 987,979 records of camera trap image sequence data and 9694 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in all 50 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1st August and 29th December each year from 2019 to 2023. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2019–2023 comprises two .csv files. The original data can be found within the SNAPSHOT USA Initiative in the Wildlife Insights platform.

Broad immunogenicity to prior SARS-CoV-2 strains and JN.1 variant elicited by XBB.1.5 vaccination in nursing home residents - Yasin Abul; Clare Nugent; Igor Vishnepolskiy; Tiffany Wallace; Evan Dickerson; Laurel Holland; Iva Esparza; Mandi Winkis; Kazi Tanvee Wali; Philip A. Chan; Rosa R. Baier; Amy Recker; et al. (GeroScience, 2024)

A sustainable blue economy may not be possible in Tanzania without cutting emissions - Ana M. Queirós; Elizabeth Talbot; Flower E. Msuya; Baraka Kuguru; Narriman Jiddawi; Shigalla Mahongo; Yohana Shaghude; Christopher Muhando; Elias Chundu; Zoe Jacobs; Sevrine Sailley; Elina A. Virtanen; et al. (Science of The Total Environment, 2024)

Obituary: Clement Allan Tisdell (1939–2022) – An ecological economist in mind, heart and soul - Boyd Dirk Blackwell; Clevo Wilson; Charles Perrings; Mohammad Alauddin; Christopher Fleming; Keith Hartley; Anya Phelan (Ecological Economics, 2024)

In-situ observations of resident space objects with the CHEOPS space telescope - Nicolas Billot; Stephan Hellmich; Willy Benz; Andrea Fortier; David Ehrenreich; Christopher Broeg; Alexis Heitzmann; Anja Bekkelien; Alexis Brandeker; Yann Alibert; Roi Alonso; Tamas Bárczy; et al. (Journal of Space Safety Engineering, 2024)

Thermal and magnetic evolution of Mercury with a layered Fe-Si(-S) core - Christopher J. Davies; Anne Pommier; Sam Greenwood; Alfred Wilson (Earth and Planetary Science Letters, 2024)

Embryonic and larval development of yellow perch ( Perca flavescens ) and its sensitivity to incubation temperature - Shamaila Fraz; Lisa Laframboise; Richard Manzon; Christopher M. Somers; Joanna Y. Wilson (Journal of Fish Biology, 2024)
The ontogenetic development in teleost fish is sensitive to temperature, and the developmental rate has a direct relationship with the environmental temperature within a species' thermal tolerance limit. Temperature determines time to and survival at hatching. Yellow perch is a North American species of ecological and commercial importance, and its phenology is vulnerable to climate change. The embryonic development of yellow perch was comparable to closely related members of the family Percidae. Developmental progression was fastest at 18°C and slowest at 12°C, with medial progression at 15°C. Time to hatch and swim‐up, feeding onset, and exogenous feeding phases were different across all incubation temperatures regardless of a gradual post‐hatch warming of the 12 and 15°C groups to a common garden temperature of 18°C. Incubation temperature may lower the rate of survival to hatch at 15°C and had complex impacts on developmental abnormalities. Temperature had significant effects on the development rate, time of hatch, survival, and incidence of developmental abnormalities. Early ontogenetic thermal history in ectotherms is an important factor determining phenotypic variation. It will be important to link the thermally induced changes in development described here to the physiological and morphological differences and to link the developmental abnormalities to functional performance.

A study of bacteria producing carbonic anhydrase enzyme for CaCO3 precipitation and soil biocementation - Wilson Mwandira; Maria Mavroulidou; Martijn Timmermans; Michael John Gunn; Christopher Gray; Leonardo Pantoja-Muñoz; Diane Purchase (Environmental Science and Pollution Research, 2024)
We study the carbonic anhydrase (CA) pathway using autochthonous CA-producing bacteria as a means of inducing calcite precipitation, which acts as a biocement to improve the engineering soil properties. Forty different microbial strains producing CA were isolated from the foundation soil of a railway embankment in Prickwillow, UK. Three of the best CA-producing strains were selected and identified by DNA sequencing as Bacillus licheniformis , Bacillus toyonensis and Bacillus pumilus with CA activity values respectively of 1.79 U/ml, 1.42 U/ml and 1.55 U/ml . To optimise the treatments, we investigated the effect of pH, temperature, zinc co-factor and cementation solution molarity on the growth and CA activity and bioprecipitates, with CO 2 added in the form of bicarbonate. Scanning electron microscope (SEM) analysis of the bioprecipitates showed that these had characteristic morphologies of calcite and vaterite crystals. The formation of calcite was further corroborated by FT-IR and Raman analysis of bioprecipitates. The precultured bacteria were injected into the fine-grained soil together with cementation solution. Unconfined compressive strength in treated soil increased up to 1 MPa, and its calcium carbonate content increased by 2.78%. This, as well as the stability of the treated soil upon water immersion, proved the biocementation of the fine-grained soil. These findings suggest the potential of employing the CA biocementation route for soil stabilisation pending further development of the technique.

Can juvenile supply predict future abundance of large-bodied reef fishes? - Shaun K. Wilson; Martial Depczynski; Christopher J. Fulton; Thomas H. Holmes; Jordan S. Goetze; Matthew J. Birt; Ben Radford; Paul Tinkler; Richard D. Evans; Molly Moustaka; Cal Faubel; Mae Noble (Marine Environmental Research, 2024)

Whole-genome analyses converge to support the Hemirotifera hypothesis within Syndermata (Gnathifera) - Alexandros Vasilikopoulos; Holger Herlyn; Diego Fontaneto; Christopher Gordon Wilson; Reuben William Nowell; Jean-François Flot; Timothy Giles Barraclough; Karine Van Doninck (Hydrobiologia, 2024)

COVID-19 and silent hypoxemia in a minimal closed-loop model of the respiratory rhythm generator - Casey O. Diekman; Peter J. Thomas; Christopher G. Wilson (Biological Cybernetics, 2024)
Silent hypoxemia, or “happy hypoxia,” is a puzzling phenomenon in which patients who have contracted COVID-19 exhibit very low oxygen saturation ( $$\text {SaO}_2$$ SaO 2 nucleus tractus solitarii are responsible for the blunted response to hypoxia. Here, we use our model to explore this hypothesis by altering the properties of the gain function representing oxygen sensing inputs to the CPG. We then vary other parameters in the model and show that oxygen carrying capacity is the most salient factor for producing silent hypoxemia. We call for clinicians to measure hematocrit as a clinical index of altered physiology in response to COVID-19 infection.

Experimental study of mechanistic factors influencing solvent-driven fractional crystallization of calcium sulfate - Ashini S. Jayasinghe; Caleb Stetson; Christopher J. Orme; Meng Shi; Aaron D. Wilson (Desalination, 2024)

High rates of erosion on a wave‐exposed fringing coral reef - Damian P. Thomson; Shannon Dee; Christopher Doropoulos; Melanie Orr; Shaun K. Wilson; Andrew S. Hoey (Limnology and Oceanography, 2024)
Erosion is a key process in shaping the physical structure of coral reefs, yet due to erosion being semi‐cryptic and difficult to quantify, information remains limited. Here, we investigate erosional processes along Ningaloo Reef, an extensive fringing coral reef in Western Australia. We employed both direct and indirect methods to measure erosion in wave‐exposed reef slopes and protected lagoonal habitats. Direct measurements of erosion on coral blocks were among the highest found globally, with total erosion of 3.07 kg m −2 yr −1 (4% from micro, 0.6% from macro, and 94% from external), whilst indirect rates were estimated at 2.4 ± 0.20 kg m −2 yr −1 (78% from parrotfish, 22% from urchins). Indirect erosion rates were influenced by the species and size of parrotfish, with Chlorurus microrhinos removing 0.44 ± 0.19 kg m −2 yr −1 (22% of parrotfish erosion). Scanning electron microscopy and computed tomography show that micro and macroborer erosion contributions to direct erosion were low, most likely due to heavy grazing by parrotfish and the short deployment period of experimental substrates. A substantial portion of external erosion on blocks (0.53 ± 0.23 kg m −2 yr −1 ) could not be attributed to bioeroders and was poorly correlated with wave exposure, suggesting processes not quantified contribute to this unaccounted aspect of erosion. Our results confirm that bioerosion by parrotfish is especially significant at Ningaloo Reef, and large‐bodied individuals of C. microrhinos are key in conserving this key ecological process.

SNAPSHOT USA 2021: A third coordinated national camera trap survey of the U nited S tates - Hila Shamon; Roi Maor; Michael V. Cove; Roland Kays; Jessie Adley; Peter D. Alexander; David N. Allen; Maximilian L. Allen; Cara L. Appel; Evan Barr; Erika L. Barthelmess; Carolina Baruzzi; et al. (Ecology, 2024)
SNAPSHOT USA is a multicontributor, long‐term camera trap survey designed to survey mammals across the United States. Participants are recruited through community networks and directly through a website application ( https://www.snapshot-usa.org/ ). The growing Snapshot dataset is useful, for example, for tracking wildlife population responses to land use, land cover, and climate changes across spatial and temporal scales. Here we present the SNAPSHOT USA 2021 dataset, the third national camera trap survey across the US. Data were collected across 109 camera trap arrays and included 1711 camera sites. The total effort equaled 71,519 camera trap nights and resulted in 172,507 sequences of animal observations. Sampling effort varied among camera trap arrays, with a minimum of 126 camera trap nights, a maximum of 3355 nights, a median 546 nights, and a mean 656 ± 431 nights. This third dataset comprises 51 camera trap arrays that were surveyed during 2019, 2020, and 2021, along with 71 camera trap arrays that were surveyed in 2020 and 2021. All raw data and accompanying metadata are stored on Wildlife Insights ( https://www.wildlifeinsights.org/ ), and are publicly available upon acceptance of the data papers. SNAPSHOT USA aims to sample multiple ecoregions in the United States with adequate representation of each ecoregion according to its relative size. Currently, the relative density of camera trap arrays varies by an order of magnitude for the various ecoregions (0.22–5.9 arrays per 100,000 km 2 ), emphasizing the need to increase sampling effort by further recruiting and retaining contributors. There are no copyright restrictions on these data. We request that authors cite this paper when using these data, or a subset of these data, for publication. Any use of trade, firm, or product names is for descriptive purposes only and does not imply endorsement by the US Government.

Avidity maturation of humoral response following primary and booster doses of BNT162b2 mRNA vaccine among nursing home residents and healthcare workers - Oladayo A. Oyebanji; Nicholas Sundheimer; Vaishnavi Ragavapuram; Brigid M. Wilson; Yasin Abul; Stefan Gravenstein; Jürgen Bosch; Christopher L. King; David H. Canaday (GeroScience, 2024)
Infections, despite vaccination, can be clinically consequential for frail nursing home residents (NHR). Poor vaccine-induced antibody quality may add risk for such subsequent infections and more severe disease. We assessed antibody binding avidity, as a surrogate for antibody quality, among NHR and healthcare workers (HCW). We longitudinally sampled 112 NHR and 52 HCWs who received the BNT162b2 mRNA vaccine after each dose up to the Wuhan-BA.4/5-based Omicron bivalent boosters. We quantified anti-spike, anti-receptor binding domain (RBD), and avidity levels to the ancestral Wuhan, Delta, and Omicron BA.1 & 4/5 strains. The primary vaccination series produced substantial anti-spike and RBD levels which were low in avidity against all strains tested. Antibody avidity progressively increased in the 6–8 months that followed. Avidity significantly increased after the 1st booster but not for subsequent boosters. This study underscores the importance of booster vaccination among NHR and HCWs. The 1st booster dose increases avidity, increasing vaccine-induced functional antibody. The higher cross-reactivity of higher avidity antibodies to other SARS-CoV-2 strains should translate to better protection from ever-evolving strains. Higher avidities may help explain how the vaccine’s protective effects persist despite waning antibody titers after each vaccine dose.

Molecular identification of Crimean-Congo haemorrhagic fever virus in Hyalomma rufipes and Amblyomma variegatum in the Upper East Region of Ghana - Seth Offei Addo; Ronald Essah Bentil; Charlotte Adwoa Addae; Bernice Olivia Ama Baako; Kevin Nii Yartey; Jane Ansah‑Owusu; Christopher Nii Laryea Tawiah-Mensah; Bright Agbodzi; Selassie Kumordjie; Clara Yeboah; Victor Asoala; James C. Dunford; et al. (Archives of Virology, 2024)

Fire sparks upslope range shifts of N orth C ascades plant species - Rachel N. Wilson; Christopher W. Kopp; Janneke Hille Ris Lambers; Amy L. Angert (Ecology, 2024)
As ongoing climate change drives suitable habitats to higher elevations, species ranges are predicted to follow. However, observed range shifts have been surprisingly variable, with most species differing in rates of upward shift and others failing to shift at all. Disturbances such as fires could play an important role in accelerating range shifts by facilitating recruitment in newly suitable habitats (leading edges) and removing adults from areas no longer suited for regeneration (trailing edges). To date, empirical evidence that fires interact with climate change to mediate elevational range shifts is scarce. Resurveying historical plots in areas that experienced climate change and fire disturbance between surveys provides an exciting opportunity to fill this gap. To investigate whether species have tended to shift upslope and if shifts depend on fires, we resurveyed historical vegetation plots in North Cascades National Park, Washington, USA, an area that has experienced warming, drying, and multiple fires since the original surveys in 1983. We quantified range shifts by synthesizing across two lines of evidence: (1) displacement at range edges and the median elevation of species occurrences, and (2) support for the inclusion of interactions among time, fire and elevation in models of species presence with elevation. Among species that experienced fire since the original survey, a plurality expanded into new habitats at their upper edge. In contrast, a plurality of species not experiencing fire showed no evidence of shifts, with the remainder exhibiting responses that were variable in magnitude and direction. Our results suggest that fires can facilitate recruitment at leading edges, while species in areas free of disturbance are more likely to experience stasis.

Stark differences in spatial gradients of Eastern oyster (Crassostrea virginica) productivity in two Florida, USA, estuaries - Laura S. Storch; David L. Kimbro; Nikki Dix; Pamela Marcum; Jason Garwood; Christopher D. Stallings; J. Wilson White (Estuarine, Coastal and Shelf Science, 2024)

Topical application of L-Menthol – Physiological and genetic considerations to assist in developing female athlete research: A narrative review - Tatiana Villegas-Serna; Laura J. Wilson; Christopher Curtis (Journal of Thermal Biology, 2024)

Energetic and exergo-environmental analysis of transcritical high-temperature heat pumps with low GWP refrigerants for industrial waste heat recovery - Adam Y. Sulaiman; Donal Cotter; Christopher Wilson; Babak Kamkari; Neil Hewitt (International Journal of Refrigeration, 2023)

Manufacturing of CD34 + HPC-enriched, high-purity mononuclear cell products from umbilical cord blood - Liam Wynn; Marnie Grace Wilson; Christopher Leonforte (Cell and Tissue Banking, 2023)

Class-based separations of mixed solid–liquid systems with condensable solvent washing and extraction: The dilemma of pizza box recycling - Hyeonseok Lee; Caleb Stetson; Christopher J. Orme; Miranda W. Kuns; Jeffrey A. Lacey; Lorenzo Vega-Montoto; Seth W. Snyder; Joseph R. Wilbanks; Julie L. Bowen; Aaron D. Wilson (Journal of Cleaner Production, 2023)

Examining the power supplied to Earth's dynamo by magnesium precipitation and radiogenic heat production - Alfred J. Wilson; Monica Pozzo; Christopher J. Davies; Andrew M. Walker; Dario Alfè (Physics of the Earth and Planetary Interiors, 2023)

Leaching of select per-/poly-fluoroalkyl substances, pharmaceuticals, and hormones through soils amended with composted biosolids - Ansley J. Levine; Eban Z. Bean; Francisca O. Hinz; P. Christopher Wilson; Alexander J. Reisinger (Journal of Environmental Management, 2023)

Conservation of skinks in New Zealand cities - Christopher K. Woolley; Stephen Hartley; John G. Innes; Danielle F. Shanahan; Yolanda van Heezik; Deborah J. Wilson; Nicola J. Nelson (Urban Ecosystems, 2023)
Urbanisation dramatically alters ecosystems, disrupting key processes and threatening species persistence. Despite growing knowledge of the impacts of cities on wildlife, particularly for birds and mammals, there remains a paucity of research on how urbanisation impacts other taxa, including reptiles. We examined how urbanisation affects skink communities across multiple New Zealand cities by undertaking pitfall trapping surveys in a range of habitats. Of the 20 endemic species thought to have been present historically in the cities, only four were captured during surveys, Oligosoma aeneum in Hamilton; O. polychroma , O. aeneum , and O. ornatum in Wellington; O. polychroma in Nelson; and O. aff. polychroma Clade 5 in Dunedin. Our results reveal highly variable patterns of occupancy, abundance, and complex associations with key threats and habitat modifications. Sites in Nelson and Wellington were much more likely to record skinks than Hamilton and Dunedin, and modelling showed abundance of O. polychroma was positively related to rat tracking rates when grass cover was low but showed a negative relationship when grass cover was high. O. polychroma body condition was negatively associated with the proportion of urban land cover (built up areas or transport infrastructure). The low number of captures of several species is concerning and long-term monitoring is needed to assess the trajectories of these vulnerable populations. Effective conservation management of urban wildlife requires knowledge of where populations exist and how urban processes affect persistence. For understudied urban-dwelling taxa such as reptiles, the lack of this information may be putting populations at risk.

An electrokinetic-biocementation study for clay stabilisation using carbonic anhydrase-producing bacteria - Wilson Mwandira; Maria Mavroulidou; Anjali Satheesh; Michael John Gunn; Christopher Gray; Diane Purchase; Jonathan Garelick (Environmental Science and Pollution Research, 2023)
This study investigates the feasibility of biocementing clay soil underneath a railway embankment of the UK rail network via carbonic anhydrase (CA) biocementation, implementing the treatments electrokinetically. Compared to previous biocementation studies using the ureolytic route, the CA pathway is attractive as CA-producing bacteria can sequester CO 2 to produce biocement. Clay soil samples were treated electrokinetically using biostimulation and bioaugmentation conditions to induce biocementation. The effects of the treatment were assessed in terms of undrained shear strength using the cone penetration test, moisture content, and calcium carbonate content measurements. Scanning electron microscopy (SEM) analyses were also conducted on soil samples before and after treatment to evaluate the reaction products. The results showed that upon biostimulation, the undrained shear strength of the soil increased uniformly throughout the soil, from 17.6 kPa (in the natural untreated state) to 106.6 kPa. SEM micrographs also showed a clear change in the soil structure upon biostimulation. Unlike biostimulation, bioaugmentation did not have the same performance, although a high amount of CaCO 3 precipitates was detected, and bacteria were observed to have entered the soil. The prospects are exciting, as it was shown that it is possible to achieve a considerable strength increase by the biostimulation of native bacteria capturing CO 2 while improving the soil strength, thus having the potential to contribute both to the resilience of existing railway infrastructure and to climate change mitigation.

Emergent role of critical interfaces in the dynamics of intensively managed landscapes - Praveen Kumar; Alison Anders; Erin Bauer; Neal E. Blair; Molly Cain; Ashlee Dere; Jennifer Druhan; Timothy Filley; Christos Giannopoulos; Allison E. Goodwell; David Grimley; Diana Karwan; et al. (Earth-Science Reviews, 2023)

Static management presents a simple solution to a dynamic fishery and conservation challenge - Christopher M. Free; Lyall F. Bellquist; Karin A. Forney; Jenn Humberstone; Kate Kauer; Qi Lee; Owen R. Liu; Jameal F. Samhouri; Jono R. Wilson; Darcy Bradley (Biological Conservation, 2023)

Holocene barrier overstepping, estuarine rollover and drainage merging in a sub-tropical bay - Wilson Fabiano Leite Galvão; Antonio Henrique da Fontoura Klein; Michel Michaelovitch de Mahiques; Christopher J. Hein; Luiz Antonio Pereira de Sousa; Andrew Cooper; Andrew Green (Marine Geology, 2023)

Effects of light and noise pollution on occupancy of gray treefrogs (Hyla versicolor) and green frogs (Lithobates clamitans) in Syracuse, NY - Jason D. Luscier; Anne Christopher; Haley Synan; Kylee B. Wilson (Urban Ecosystems, 2023)

CH 4 and N 2 O emissions from smallholder agricultural systems on tropical peatlands in Southeast Asia - Antonio Jonay Jovani‐Sancho; Patrick O'Reilly; Gusti Anshari; Xin Yi Chong; Neil Crout; Christopher D. Evans; Stephanie Evers; Jing Ye Gan; Christopher N. Gibbins; Evi Gusmayanti; Jamaludin Jamaludin; Adi Jaya; et al. (Global Change Biology, 2023)
There are limited data for greenhouse gas (GHG) emissions from smallholder agricultural systems in tropical peatlands, with data for non‐CO 2 emissions from human‐influenced tropical peatlands particularly scarce. The aim of this study was to quantify soil CH 4 and N 2 O fluxes from smallholder agricultural systems on tropical peatlands in Southeast Asia and assess their environmental controls. The study was carried out in four regions in Malaysia and Indonesia. CH 4 and N 2 O fluxes and environmental parameters were measured in cropland, oil palm plantation, tree plantation and forest. Annual CH 4 emissions (in kg CH 4 ha −1 year −1 ) were: 70.7 ± 29.5, 2.1 ± 1.2, 2.1 ± 0.6 and 6.2 ± 1.9 at the forest, tree plantation, oil palm and cropland land‐use classes, respectively. Annual N 2 O emissions (in kg N 2 O ha −1 year −1 ) were: 6.5 ± 2.8, 3.2 ± 1.2, 21.9 ± 11.4 and 33.6 ± 7.3 in the same order as above, respectively. Annual CH 4 emissions were strongly determined by water table depth (WTD) and increased exponentially when annual WTD was above −25 cm. In contrast, annual N 2 O emissions were strongly correlated with mean total dissolved nitrogen (TDN) in soil water, following a sigmoidal relationship, up to an apparent threshold of 10 mg N L −1 beyond which TDN seemingly ceased to be limiting for N 2 O production. The new emissions data for CH 4 and N 2 O presented here should help to develop more robust country level ‘emission factors’ for the quantification of national GHG inventory reporting. The impact of TDN on N 2 O emissions suggests that soil nutrient status strongly impacts emissions, and therefore, policies which reduce N‐fertilisation inputs might contribute to emissions mitigation from agricultural peat landscapes. However, the most important policy intervention for reducing emissions is one that reduces the conversion of peat swamp forest to agriculture on peatlands in the first place.

Can homogeneous nucleation resolve the inner core nucleation paradox? - Alfred J. Wilson; Dario Alfè; Andrew M. Walker; Christopher J. Davies (Earth and Planetary Science Letters, 2023)

Seagrass Abundance Predicts Surficial Soil Organic Carbon Stocks Across the Range of Thalassia testudinum in the Western North Atlantic - James W. Fourqurean; Justin E. Campbell; O. Kennedy Rhoades; Calvin J. Munson; Johannes R. Krause; Andrew H. Altieri; James G. Douglass; Kenneth L. Heck; Valerie J. Paul; Anna R. Armitage; Savanna C. Barry; Enrique Bethel; et al. (Estuaries and Coasts, 2023)

Environmental risk assessment for fecal contamination sources in urban and peri-urban estuaries, in Escambia and Santa Rosa counties, FL, USA - Ronell S. H. Bridgemohan; Matthew J. Deitch; Tesfay Gebremicael; Matthew R. Whiles; P. Christopher Wilson; Dave Bachoon; Israel Tharpe (Environmental Monitoring and Assessment, 2023)

Impact of the 2014–2016 marine heatwave on US and Canada West Coast fisheries: Surprises and lessons from key case studies - Christopher M. Free; Sean C. Anderson; Elizabeth A. Hellmers; Barbara A. Muhling; Michael O. Navarro; Kate Richerson; Lauren A. Rogers; William H. Satterthwaite; Andrew R. Thompson; Jenn M. Burt; Steven D. Gaines; Kristin N. Marshall; et al. (Fish and Fisheries, 2023)
Marine heatwaves are increasingly affecting marine ecosystems, with cascading impacts on coastal economies, communities, and food systems. Studies of heatwaves provide crucial insights into potential ecosystem shifts under future climate change and put fisheries social‐ecological systems through “stress tests” that expose both vulnerabilities and resilience. The 2014–16 Northeast Pacific heatwave was the strongest and longest marine heatwave on record and resulted in profound ecological changes that impacted fisheries, fisheries management, and human livelihoods. Here, we synthesize the impacts of the 2014–2016 marine heatwave on US and Canada West Coast fisheries and extract key lessons for preparing global fisheries science, management, and industries for the future. We set the stage with a brief review of the impacts of the heatwave on marine ecosystems and the first systematic analysis of the economic impacts of these changes on commercial and recreational fisheries. We then examine ten key case studies that provide instructive examples of the complex and surprising challenges that heatwaves pose to fisheries social‐ecological systems. These reveal important insights into improving the resilience of monitoring and management and increasing adaptive capacity to future stressors. Key recommendations include: (1) expanding monitoring to enhance mechanistic understanding, provide early warning signals, and improve predictions of impacts; (2) increasing the flexibility, adaptiveness, and inclusiveness of management where possible; (3) using simulation testing to help guide management decisions; and (4) enhancing the adaptive capacity of fishing communities by promoting engagement, flexibility, experimentation, and failsafes. These advancements are important as global fisheries prepare for a changing ocean.

Stable isotopes and foraging behaviors support the role of antipredator benefits in driving the association between two marine fishes - Christopher R. Haak; Michael Power; Alexander D. M. Wilson; Andy J. Danylchuk (Oecologia, 2023)

Comprehensive ECG reference intervals in C57BL/6N substrains provide a generalizable guide for cardiac electrophysiology studies in mice - Manuela A. Oestereicher; Janine M. Wotton; Shinya Ayabe; Ghina Bou About; Tsz Kwan Cheng; Jae-Hoon Choi; Dave Clary; Emily M. Dew; Lahcen Elfertak; Alain Guimond; Hamed Haseli Mashhadi; Jason D. Heaney; et al. (Mammalian Genome, 2023)
Reference ranges provide a powerful tool for diagnostic decision-making in clinical medicine and are enormously valuable for understanding normality in pre-clinical scientific research that uses in vivo models. As yet, there are no published reference ranges for electrocardiography (ECG) in the laboratory mouse. The first mouse-specific reference ranges for the assessment of electrical conduction are reported herein generated from an ECG dataset of unprecedented scale. International Mouse Phenotyping Consortium data from over 26,000 conscious or anesthetized C57BL/6N wildtype control mice were stratified by sex and age to develop robust ECG reference ranges. Interesting findings include that heart rate and key elements from the ECG waveform (RR-, PR-, ST-, QT-interval, QT corrected, and QRS complex) demonstrate minimal sexual dimorphism. As expected, anesthesia induces a decrease in heart rate and was shown for both inhalation (isoflurane) and injectable (tribromoethanol) anesthesia. In the absence of pharmacological, environmental, or genetic challenges, we did not observe major age-related ECG changes in C57BL/6N-inbred mice as the differences in the reference ranges of 12-week-old compared to 62-week-old mice were negligible. The generalizability of the C57BL/6N substrain reference ranges was demonstrated by comparison with ECG data from a wide range of non-IMPC studies. The close overlap in data from a wide range of mouse strains suggests that the C57BL/6N-based reference ranges can be used as a robust and comprehensive indicator of normality. We report a unique ECG reference resource of fundamental importance for any experimental study of cardiac function in mice.

Macroalgae exhibit diverse responses to human disturbances on coral reefs - Sara E. Cannon; Simon D. Donner; Angela Liu; Pedro C. González Espinosa; Andrew H. Baird; Julia K. Baum; Andrew G. Bauman; Maria Beger; Cassandra E. Benkwitt; Matthew J. Birt; Yannick Chancerelle; Joshua E. Cinner; et al. (Global Change Biology, 2023)
Scientists and managers rely on indicator taxa such as coral and macroalgal cover to evaluate the effects of human disturbance on coral reefs, often assuming a universally positive relationship between local human disturbance and macroalgae. Despite evidence that macroalgae respond to local stressors in diverse ways, there have been few efforts to evaluate relationships between specific macroalgae taxa and local human‐driven disturbance. Using genus‐level monitoring data from 1205 sites in the Indian and Pacific Oceans, we assess whether macroalgae percent cover correlates with local human disturbance while accounting for factors that could obscure or confound relationships. Assessing macroalgae at genus level revealed that no genera were positively correlated with all human disturbance metrics. Instead, we found relationships between the division or genera of algae and specific human disturbances that were not detectable when pooling taxa into a single functional category, which is common to many analyses. The convention to use percent cover of macroalgae as an indication of local human disturbance therefore likely obscures signatures of local anthropogenic threats to reefs. Our limited understanding of relationships between human disturbance, macroalgae taxa, and their responses to human disturbances impedes the ability to diagnose and respond appropriately to these threats.

Climate-driven shifts in pelagic fish distributions in a rapidly changing Pacific Arctic - Robert M. Levine; Alex De Robertis; Daniel Grünbaum; Sharon Wildes; Edward V. Farley; Phyllis J. Stabeno; Christopher D. Wilson (Deep Sea Research Part II: Topical Studies in Oceanography, 2023)

Aerobically trained older adults show impaired resting, but preserved exercise-induced circulating progenitor cell count, which was not improved by sprint interval training - Zerbu Yasar; Mark D. Ross; Christopher J. Gaffney; Ruth D. Postlethwaite; Russell Wilson; Lawrence D. Hayes (Pflügers Archiv - European Journal of Physiology, 2023)
Older adults exhibit a reduced number and function of CD34 + circulating progenitor cells (CPC), a known risk factor for cardiovascular disease. Exercise promotes the mobilisation of CPCs from bone marrow, so whether ageing per se or physical inactivity in older age reduces CPCs is unknown. Thus, this study examined the effect of age on resting and exercise-induced changes in CPCs in aerobically trained adults and the effect of 8 weeks of sprint interval training (SIT) on resting and exercise-induced CPCs in older adults. Twelve young (22–34 years) and nine older (63–70 years) adults participated in the study. Blood was sampled pre and immediately post a graded exercise test to exhaustion in both groups. Older participants repeated the process after 8 weeks of SIT (3 × 20 s ‘all-out’ sprints, 2 × a week). Total CPCs (CD34 + ) and endothelial progenitor cells (EPCs: CD34 + KDR + ) were determined by flow cytometry. Older adults exhibited lower basal total CD34 + CPCs (828 ± 314 vs. 1186 ± 272 cells·mL −1 , p = 0.0149) and CD34 + KDR + EPCs (177 ± 128 vs. 335 ± 92 cells·mL −1 , p = 0.007) than younger adults. The maximal exercise test increased CPCs in young (CD34 + : p = 0.004; CD34 + KDR + : p = 0.017) and older adults (CD34 + : p < 0.001; CD34 + KDR + : p = 0.008), without difference between groups ( p = 0.211). SIT did not alter resting or exercise-induced changes in CPCs in the older cohort ( p > 0.232). This study suggests age per se does not impair exercise-induced CPC counts, but does lower resting CPC counts.

Low diversity and microdiversity of comammox bacteria in wastewater systems suggest specific adaptations within the Ca. Nitrospira nitrosa cluster - Irmarie Cotto; Katherine J. Vilardi; Linxuan Huo; Emily C. Fogarty; Wendell Khunjar; Christopher Wilson; Haydee De Clippeleir; Kevin Gilmore; Erika Bailey; Sebastian Lücker; Ameet J. Pinto (Water Research, 2023)

Modifying a pelagic trawl to better retain small Arctic fishes - Alex De Robertis; Robert Levine; Kresimir Williams; Christopher Wilson (Deep Sea Research Part II: Topical Studies in Oceanography, 2023)

Common genetic risk factors in ASD and ADHD co-occurring families - Anbo Zhou; Xiaolong Cao; Vaidhyanathan Mahaganapathy; Marco Azaro; Christine Gwin; Sherri Wilson; Steven Buyske; Christopher W. Bartlett; Judy F. Flax; Linda M. Brzustowicz; Jinchuan Xing (Human Genetics, 2023)

T-cell cellular stress and reticulocyte signatures, but not loss of naïve T lymphocytes, characterize severe COVID-19 in older adults - Mladen Jergović; Makiko Watanabe; Ruchika Bhat; Christopher P. Coplen; Sandip A. Sonar; Rachel Wong; Yvonne Castaneda; Lisa Davidson; Mrinalini Kala; Rachel C. Wilson; Homer L. Twigg; Kenneth Knox; et al. (GeroScience, 2023)

SNAPSHOT USA 2020: A second coordinated national camera trap survey of the United States during the COVID ‐19 pandemic - Roland Kays; Michael V. Cove; Jose Diaz; Kimberly Todd; Claire Bresnan; Matt Snider; Thomas E. Lee; Jonathan G. Jasper; Brianna Douglas; Anthony P. Crupi; Katherine C. B. Weiss; Helen Rowe; et al. (Ecology, 2022)
Managing wildlife populations in the face of global change requires regular data on the abundance and distribution of wild animals, but acquiring these over appropriate spatial scales in a sustainable way has proven challenging. Here we present the data from Snapshot USA 2020, a second annual national mammal survey of the USA. This project involved 152 scientists setting camera traps in a standardized protocol at 1485 locations across 103 arrays in 43 states for a total of 52,710 trap‐nights of survey effort. Most (58) of these arrays were also sampled during the same months (September and October) in 2019, providing a direct comparison of animal populations in 2 years that includes data from both during and before the COVID‐19 pandemic. All data were managed by the eMammal system, with all species identifications checked by at least two reviewers. In total, we recorded 117,415 detections of 78 species of wild mammals, 9236 detections of at least 43 species of birds, 15,851 detections of six domestic animals and 23,825 detections of humans or their vehicles. Spatial differences across arrays explained more variation in the relative abundance than temporal variation across years for all 38 species modeled, although there are examples of significant site‐level differences among years for many species. Temporal results show how species allocate their time and can be used to study species interactions, including between humans and wildlife. These data provide a snapshot of the mammal community of the USA for 2020 and will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, and the impacts of species interactions on daily activity patterns. There are no copyright restrictions, and please cite this paper when using these data, or a subset of these data, for publication.

A fly GWAS for purine metabolites identifies human FAM214 homolog medusa, which acts in a conserved manner to enhance hyperuricemia-driven pathologies by modulating purine metabolism and the inflammatory response - Tyler A. U. Hilsabeck; Ru Liu-Bryan; Tracy Guo; Kenneth A. Wilson; Neelanjan Bose; Daniel Raftery; Jennifer N. Beck; Sven Lang; Kelly Jin; Christopher S. Nelson; Tal Oron; Marshall Stoller; et al. (GeroScience, 2022)

Obstructive sleep apnea and white matter hyperintensities: correlation or causation? - Noah C. Schammel; Trevor VandeWater; Stella Self; Christopher Wilson; Christine M. G. Schammel; Ronald Cowley; Dominic B. Gault; Lee A. Madeline (Brain Imaging and Behavior, 2022)

An Exploratory Survey on the Care for Ataxic Patients in the American Continents and the Caribbean - Laura Bannach Jardim; Ali Hasan; Sheng-han Kuo; Jonathan Javier Magaña; Marcondes França; Wilson Marques; Claudia Camejo; Luiz Carlos Santana-da-Silva; Emília Embiruçu Leão; Gisele Espíndola; Francisca Canals; Marcelo Miranda; et al. (The Cerebellum, 2022)

The contribution of macroalgae‐associated fishes to small‐scale tropical reef fisheries - Shaun K. Wilson; Christopher J. Fulton; Nicholas A.J. Graham; Rene A. Abesamis; Charlotte Berkström; Darren J. Coker; Martial Depczynski; Richard D. Evans; Rebecca Fisher; Jordan Goetze; Andrew Hoey; Thomas H. Holmes; et al. (Fish and Fisheries, 2022)
Macroalgae‐dominated reefs are a prominent habitat in tropical seascapes that support a diversity of fishes, including fishery target species. To what extent, then, do macroalgal habitats contribute to small‐scale tropical reef fisheries? To address this question we: (1) Quantified the macroalgae‐associated fish component in catches from 133 small‐scale fisheries, (2) Compared life‐history traits relevant to fishing (e.g. growth, longevity) in macroalgal and coral‐associated fishes, (3) Examined how macroalgae‐associated species can influence catch diversity, trophic level and vulnerability and (4) Explored how tropical fisheries change with the expansion of macroalgal habitats using a case study of fishery‐independent data for Seychelles. Fish that utilised macroalgal habitats comprise 24% of the catch, but very few fished species relied entirely on macroalgal or coral habitats post‐settlement. Macroalgal and coral‐associated fishes had similar life‐history traits, although vulnerability to fishing declined with increasing contribution of macroalgae association to the catch, whilst mean trophic level and diversity peaked when macroalgal‐associated fish accounted for 20%–30% of catches. The Seychelles case study revealed similar total fish biomass on macroalgal and coral reefs, although the biomass of primary target species increased as macroalgae cover expanded. Our findings reinforce that multiple habitat types are needed to support tropical fishery stability and sustainability. Whilst coral habitats have been the focus of tropical fisheries management, we show the potential for macroalgae‐associated fish to support catch size and diversity in ways that reduce vulnerability to overfishing. This is pertinent to seascapes where repeated disturbances are facilitating the replacement of coral reef with macroalgal habitats.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Mapping Seafloor Relative Reflectance and Assessing Coral Reef Morphology with EAARL-B Topobathymetric Lidar Waveforms - Nicholas Wilson; Christopher E. Parrish; Tim Battista; C. Wayne Wright; Bryan Costa; Richard K. Slocum; Jennifer A. Dijkstra; Matthew T. Tyler (Estuaries and Coasts, 2022)
Topobathymetric lidar is becoming an increasingly valuable tool for benthic habitat mapping, enabling safe, efficient data acquisition over coral reefs and other fragile ecosystems. In 2014, a novel topobathymetric lidar system, the Experimental Advanced Airborne Research Lidar-B (EAARL-B), was used to acquire data in priority habitat areas in the U.S. Virgin Islands (USVI), spanning the 0–44-m depth range. In this study, new algorithms and procedures were developed for generating seafloor relative reflectance, along with a suite of shape-based waveform features from EAARL-B. Waveform features were then correlated with percent cover of coral morphologies, domed and branched, and total cover of hard and soft corals. Results show that the EAARL-B can be used to produce useful seafloor relative reflectance mosaics and also that the additional waveform shape-based features contain additional information that may benefit habitat classification—specifically, to aid in distinguishing among hard corals and their coral morphologies, domed and branched. Knowing the spatial extent of changes in coral communities is important to the understanding of resiliency of coral reefs under stress from human impacts.

Expert range maps of global mammal distributions harmonised to three taxonomic authorities - Charles J. Marsh; Yanina V. Sica; Connor J. Burgin; Wendy A. Dorman; Robert C. Anderson; Isabel del Toro Mijares; Jessica G. Vigneron; Vijay Barve; Victoria L. Dombrowik; Michelle Duong; Robert Guralnick; Julie A. Hart; et al. (Journal of Biogeography, 2022)
Aim Comprehensive, global information on species' occurrences is an essential biodiversity variable and central to a range of applications in ecology, evolution, biogeography and conservation. Expert range maps often represent a species' only available distributional information and play an increasing role in conservation assessments and macroecology. We provide global range maps for the native ranges of all extant mammal species harmonised to the taxonomy of the Mammal Diversity Database (MDD) mobilised from two sources, the Handbook of the Mammals of the World (HMW) and the Illustrated Checklist of the Mammals of the World (CMW). Location Global. Taxon All extant mammal species. Methods Range maps were digitally interpreted, georeferenced, error‐checked and subsequently taxonomically aligned between the HMW (6253 species), the CMW (6431 species) and the MDD taxonomies (6362 species). Results Range maps can be evaluated and visualised in an online map browser at Map of Life ( mol.org ) and accessed for individual or batch download for non‐commercial use. Main conclusion Expert maps of species' global distributions are limited in their spatial detail and temporal specificity, but form a useful basis for broad‐scale characterizations and model‐based integration with other data. We provide georeferenced range maps for the native ranges of all extant mammal species as shapefiles, with species‐level metadata and source information packaged together in geodatabase format. Across the three taxonomic sources our maps entail, there are 1784 taxonomic name differences compared to the maps currently available on the IUCN Red List website. The expert maps provided here are harmonised to the MDD taxonomic authority and linked to a community of online tools that will enable transparent future updates and version control.

Effects of polyaluminum chloride (PAX-18) on the relationship between predatory fungi and Lecane rotifers - Edyta Fiałkowska; Wojciech Fiałkowski; Christopher G. Wilson; Agnieszka Pajdak-Stós (Environmental Science and Pollution Research, 2022)
PAX-18 (polyaluminum chloride) is frequently used in WWTPs (wastewater treatment plants) to overcome sludge bulking. An alternative biological method is the usage of Lecane rotifers, which can be endangered by predacious fungi. We investigated the influence of different PAX-18 concentrations on the relationship between Lecane inermis and predacious fungi ( Zoophagus and Lecophagus ) differing in feeding mode. High PAX concentration (6 mg Al 3+ L −1 ) strongly limited the number of the rotifers, which in low concentration (1.2 mg Al 3+ L −1 ), after an initial decline, increased, but significantly slower than in control. Under the simultaneous influence of Lecophagus and PAX, rotifers were driven almost extinct at the high concentration, but survived at the lower concentration and increased in the control. When treated with Zoophagus , only one or two rotifers survived in treatments and control. High concentrations of PAX significantly restricted the growth of fungi, whereas in low concentrations and control conditions, their length increased, with Zoophagus growing much quicker than Lecophagus . Zoophagus was significantly more efficient in trapping rotifers regardless of PAX concentration. The trapping ability of mycelium following extended exposure to PAX was strongly limited at high concentrations, in comparison to control. Conidia of Zoophagus turned out to be considerably more resistant to PAX-18 and starvation than Lecophagus conidia.

Correction to: Evolution and diversity of the angiosperm anther: trends in function and development - Johanna Åstrand; Christopher Knight; Jordan Robson; Behzad Talle; Zoe A. Wilson (Plant Reproduction, 2021)
Unfortunately, the original publication of the article has an error in the labelling on Fig. 3. The correct figure is given in this correction.

Evolution and diversity of the angiosperm anther: trends in function and development - Johanna Åstrand; Christopher Knight; Jordan Robson; Behzad Talle; Zoe A. Wilson (Plant Reproduction, 2021)
Key message Anther development and dehiscence is considered from an evolutionary perspective to identify drivers for differentiation, functional conservation and to identify key questions for future male reproduction research. Abstract Development of viable pollen and its timely release from the anther are essential for fertilisation of angiosperm flowers. The formation and subsequent dehiscence of the anther are under tight regulatory control, and these processes are remarkably conserved throughout the diverse families of the angiosperm clade. Anther development is a complex process, which requires timely formation and communication between the multiple somatic anther cell layers (the epidermis, endothecium, middle layer and tapetum) and the developing pollen. These layers go through regulated development and selective degeneration to facilitate the formation and ultimate release of the pollen grains. Insight into the evolution and divergence of anther development and dehiscence, especially between monocots and dicots, is driving greater understanding of the male reproductive process and increased, resilient crop yields. This review focuses on anther structure from an evolutionary perspective by highlighting their diversity across plant species. We summarise new findings that illustrate the complexities of anther development and evaluate how they challenge established models of anther form and function, and how they may help to deliver future sustainable crop yields.

Functional traits driving species role in the structure of terrestrial vertebrate scavenger networks - Esther Sebastián‐González; Zebensui Morales‐Reyes; Francisco Botella; Lara Naves‐Alegre; Juan M. Pérez‐García; Patricia Mateo‐Tomás; Pedro P. Olea; Marcos Moleón; Jomar Magalhães Barbosa; Fernando Hiraldo; Eneko Arrondo; José A. Donázar; et al. (Ecology, 2021)
Species assemblages often have a non‐random nested organization, which in vertebrate scavenger (carrion‐consuming) assemblages is thought to be driven by facilitation in competitive environments. However, not all scavenger species play the same role in maintaining assemblage structure, as some species are obligate scavengers (i.e., vultures) and others are facultative, scavenging opportunistically. We used a database with 177 vertebrate scavenger species from 53 assemblages in 22 countries across five continents to identify which functional traits of scavenger species are key to maintaining the scavenging network structure. We used network analyses to relate ten traits hypothesized to affect assemblage structure with the “role” of each species in the scavenging assemblage in which it appeared. We characterized the role of a species in terms of both the proportion of monitored carcasses on which that species scavenged, or scavenging breadth (i.e., the species “normalized degree”), and the role of that species in the nested structure of the assemblage (i.e., the species “paired nested degree”), therefore identifying possible facilitative interactions among species. We found that species with high olfactory acuity, social foragers, and obligate scavengers had the widest scavenging breadth. We also found that social foragers had a large paired nested degree in scavenger assemblages, probably because their presence is easier to detect by other species to signal carcass occurrence. Our study highlights differences in the functional roles of scavenger species and can be used to identify key species for targeted conservation to maintain the ecological function of scavenger assemblages.

Interactive effects of sediments and urchins on the composition and structure of tropical macroalgal assemblages - Rosalie J. Harris; Shaun K. Wilson; Christopher J. Fulton (Marine Biology, 2021)

Genome sequencing in families with congenital limb malformations - Jonas Elsner; Martin A. Mensah; Manuel Holtgrewe; Jakob Hertzberg; Stefania Bigoni; Andreas Busche; Marie Coutelier; Deepthi C. de Silva; Nursel Elçioglu; Isabel Filges; Erica Gerkes; Katta M. Girisha; et al. (Human Genetics, 2021)
The extensive clinical and genetic heterogeneity of congenital limb malformation calls for comprehensive genome-wide analysis of genetic variation. Genome sequencing (GS) has the potential to identify all genetic variants. Here we aim to determine the diagnostic potential of GS as a comprehensive one-test-for-all strategy in a cohort of undiagnosed patients with congenital limb malformations. We collected 69 cases (64 trios, 1 duo, 5 singletons) with congenital limb malformations with no molecular diagnosis after standard clinical genetic testing and performed genome sequencing. We also developed a framework to identify potential noncoding pathogenic variants. We identified likely pathogenic/disease-associated variants in 12 cases (17.4%) including four in known disease genes, and one repeat expansion in HOXD13 . In three unrelated cases with ectrodactyly, we identified likely pathogenic variants in UBA2 , establishing it as a novel disease gene. In addition, we found two complex structural variants (3%). We also identified likely causative variants in three novel high confidence candidate genes. We were not able to identify any noncoding variants. GS is a powerful strategy to identify all types of genomic variants associated with congenital limb malformation, including repeat expansions and complex structural variants missed by standard diagnostic approaches. In this cohort, no causative noncoding SNVs could be identified.

Microbial diversity and activity in Southern California salterns and bitterns: analogues for remnant ocean worlds - Benjamin Klempay; Nestor Arandia‐Gorostidi; Anne E. Dekas; Douglas H. Bartlett; Christopher E. Carr; Peter T. Doran; Avishek Dutta; Natalia Erazo; Luke A. Fisher; Jennifer B. Glass; Alexandra Pontefract; Sanjoy M. Som; et al. (Environmental Microbiology, 2021)
Summary Concurrent osmotic and chaotropic stress make MgCl 2 ‐rich brines extremely inhospitable environments. Understanding the limits of life in these brines is essential to the search for extraterrestrial life on contemporary and relict ocean worlds, like Mars, which could host similar environments. We sequenced environmental 16S rRNA genes and quantified microbial activity across a broad range of salinity and chaotropicity at a Mars‐analogue salt harvesting facility in Southern California, where seawater is evaporated in a series of ponds ranging from kosmotropic NaCl brines to highly chaotropic MgCl 2 brines. Within NaCl brines, we observed a proliferation of specialized halophilic Euryarchaeota, which corresponded closely with the dominant taxa found in salterns around the world. These communities were characterized by very slow growth rates and high biomass accumulation. As salinity and chaotropicity increased, we found that the MgCl 2 ‐rich brines eventually exceeded the limits of microbial activity. We found evidence that exogenous genetic material is preserved in these chaotropic brines, producing an unexpected increase in diversity in the presumably sterile MgCl 2 ‐saturated brines. Because of their high potential for biomarker preservation, chaotropic brines could therefore serve as repositories of genetic biomarkers from nearby environments (both on Earth and beyond) making them prime targets for future life‐detection missions.

Accidents alter animal fitness landscapes - Rebecca Wheatley; Jessie C. Buettel; Barry W. Brook; Christopher N. Johnson; Rory P. Wilson (Ecology Letters, 2021)
Animals alter their habitat use in response to the energetic demands of movement (‘energy landscapes’) and the risk of predation (‘the landscape of fear’). Recent research suggests that animals also select habitats and move in ways that minimise their chance of temporarily losing control of movement and thereby suffering slips, falls, collisions or other accidents, particularly when the consequences are likely to be severe (resulting in injury or death). We propose that animals respond to the costs of an ‘accident landscape’ in conjunction with predation risk and energetic costs when deciding when, where, and how to move in their daily lives. We develop a novel theoretical framework describing how features of physical landscapes interact with animal size, morphology, and behaviour to affect the risk and severity of accidents, and predict how accident risk might interact with predation risk and energetic costs to dictate movement decisions across the physical landscape. Future research should focus on testing the hypotheses presented here for different real‐world systems to gain insight into the relative importance of theorised effects in the field.

Between a rock and a hard place: rugged terrain features and human disturbance affect behaviour and habitat use of Sumatran elephants in Aceh, Sumatra, Indonesia - Gaius Wilson; Russell J. Gray; Radinal Radinal; Hasanuddin Hasanuddin; Wahdi Azmi; Arman Sayuti; Hambal Muhammad; Abdullah Abdullah; B. S. Nazamuddin; Hizir Sofyan; Heidi S. Riddle; Christopher Stremme; et al. (Biodiversity and Conservation, 2021)

Lung abnormalities do not influence aerobic capacity in school children born preterm - Christopher A. O’Dea; Karla Logie; Andrew C. Wilson; J. Jane Pillow; Conor Murray; Georgia Banton; Shannon J. Simpson; Graham L. Hall; Andrew Maiorana (European Journal of Applied Physiology, 2021)

A chemical structure-based approach for estimating the added levels of flavourings to foods for the purpose of assessing consumer intake - Maria Bastaki; Michel Aubanel; Heidi Bialk; Christopher Choi; Jan Demyttenaere; Malick Maodo Diop; Sylvain Etter; Xing Han; Mihoko Koyanagi; Gerhard Krammer; Jürgen Schnabel; Cody L. Wilson; et al. (Food Additives & Contaminants: Part A, 2021)

NEOTROPICAL CARNIVORES: a data set on carnivore distribution in the Neotropics - Mariana Nagy‐Reis; Júlia Emi de Faria Oshima; Claudia Zukeran Kanda; Francesca Belem Lopes Palmeira; Fabiano Rodrigues de Melo; Ronaldo Gonçalves Morato; Lilian Bonjorne; Marcelo Magioli; Caroline Leuchtenberger; Fabio Rohe; Frederico Gemesio Lemos; Felipe Martello; et al. (Ecology, 2020)
Mammalian carnivores are considered a key group in maintaining ecological health and can indicate potential ecological integrity in landscapes where they occur. Carnivores also hold high conservation value and their habitat requirements can guide management and conservation plans. The order Carnivora has 84 species from 8 families in the Neotropical region: Canidae; Felidae; Mephitidae; Mustelidae; Otariidae; Phocidae; Procyonidae; and Ursidae. Herein, we include published and unpublished data on native terrestrial Neotropical carnivores (Canidae; Felidae; Mephitidae; Mustelidae; Procyonidae; and Ursidae). NEOTROPICAL CARNIVORES is a publicly available data set that includes 99,605 data entries from 35,511 unique georeferenced coordinates. Detection/non‐detection and quantitative data were obtained from 1818 to 2018 by researchers, governmental agencies, non‐governmental organizations, and private consultants. Data were collected using several methods including camera trapping, museum collections, roadkill, line transect, and opportunistic records. Literature (peer‐reviewed and grey literature) from Portuguese, Spanish and English were incorporated in this compilation. Most of the data set consists of detection data entries (n = 79,343; 79.7%) but also includes non‐detection data (n = 20,262; 20.3%). Of those, 43.3% also include count data (n = 43,151). The information available in NEOTROPICAL CARNIVORES will contribute to macroecological, ecological, and conservation questions in multiple spatio‐temporal perspectives. As carnivores play key roles in trophic interactions, a better understanding of their distribution and habitat requirements are essential to establish conservation management plans and safeguard the future ecological health of Neotropical ecosystems. Our data paper, combined with other large‐scale data sets, has great potential to clarify species distribution and related ecological processes within the Neotropics. There are no copyright restrictions and no restriction for using data from this data paper, as long as the data paper is cited as the source of the information used. We also request that users inform us of how they intend to use the data.

Discovery of a Highly Selective Sigma-2 Receptor Ligand, 1-(4-(6,7-Dimethoxy-3,4-dihydroisoquinolin-2(1H)-yl)butyl)-3-methyl-1H-benzo[d]imidazol-2(3H)-one (CM398), with Drug-Like Properties and Antinociceptive Effects In Vivo - Sebastiano Intagliata; Abhisheak Sharma; Tamara I. King; Christophe Mesangeau; Michael Seminerio; Frederick T. Chin; Lisa L. Wilson; Rae R. Matsumoto; Jay P. McLaughlin; Bonnie A. Avery; Christopher R. McCurdy (The AAPS Journal, 2020)

Effects of body size on estimation of mammalian area requirements - Michael J. Noonan; Christen H. Fleming; Marlee A. Tucker; Roland Kays; Autumn‐Lynn Harrison; Margaret C. Crofoot; Briana Abrahms; Susan C. Alberts; Abdullahi H. Ali; Jeanne Altmann; Pamela Castro Antunes; Nina Attias; et al. (Conservation Biology, 2020)
Accurately quantifying species’ area requirements is a prerequisite for effective area‐based conservation. This typically involves collecting tracking data on species of interest and then conducting home‐range analyses. Problematically, autocorrelation in tracking data can result in space needs being severely underestimated. Based on the previous work, we hypothesized the magnitude of underestimation varies with body mass, a relationship that could have serious conservation implications. To evaluate this hypothesis for terrestrial mammals, we estimated home‐range areas with global positioning system (GPS) locations from 757 individuals across 61 globally distributed mammalian species with body masses ranging from 0.4 to 4000 kg. We then applied block cross‐validation to quantify bias in empirical home‐range estimates. Area requirements of mammals 1, meaning the scaling of the relationship changed substantially at the upper end of the mass spectrum.

Modifying effects of a cobble substrate on thermal environments and implications for embryonic development in lake whitefish ( Coregonus clupeaformis ) - Christopher Thome; Taylor Laframboise; Charles Mitz; Eric Clancy; Jacob Bates; Christopher M. Somers; Richard G. Manzon; Joanna Y. Wilson; John M. Gunn; Douglas R. Boreham (Journal of Fish Biology, 2020)
A laboratory flume was constructed to examine substrate effects on aquatic development. The flume was designed as a once‐through system with a submerged cobble‐filled corebox. Lake whitefish ( Coregonus clupeaformis ) embryos and temperature probes were deployed at multiple sites within the cobble and in the open water channel. Embryos were incubated in the flume for two different experimental periods: one to examine substrate impacts during natural lake cooling (37 days: 5 December 2016 to 10 January 2017) and the second to investigate substrate effects while administering a twice weekly 1 h heat shock (51 days: 11 January to 2 March 2017). During incubation, no significant difference was found in the average temperature between locations; however, temperatures were more stable within the cobble. Following both incubation periods, embryos retrieved from the cobble were significantly smaller in both dry mass and body length by up to 20%. These results demonstrate differences between embryos submerged in a cobble substrate and in the open water column, highlighting the need to consider the physical influences from the incubation environment when assessing development effects as part of any scientific study or environmental assessment.

Macroalgal meadow habitats support fish and fisheries in diverse tropical seascapes - Christopher J. Fulton; Charlotte Berkström; Shaun K. Wilson; Rene A. Abesamis; Michael Bradley; Carolina Åkerlund; Luke T. Barrett; Abner A. Bucol; Dinorah H. Chacin; Karen M. Chong‐Seng; Darren J. Coker; Martial Depczynski; et al. (Fish and Fisheries, 2020)
Canopy‐forming macroalgae can construct extensive meadow habitats in tropical seascapes occupied by fishes that span a diversity of taxa, life‐history stages and ecological roles. Our synthesis assessed whether these tropical macroalgal habitats have unique fish assemblages, provide fish nurseries and support local fisheries. We also applied a meta‐analysis of independent surveys across 23 tropical reef locations in 11 countries to examine how macroalgal canopy condition is related to the abundance of macroalgal‐associated fishes. Over 627 fish species were documented in tropical macroalgal meadows, with 218 of these taxa exhibiting higher local abundance within this habitat (cf. nearby coral reef) during at least one life‐history stage. Major overlap (40%–43%) in local fish species richness among macroalgal and seagrass or coral reef habitats suggest macroalgal meadows may provide an important habitat refuge. Moreover, the prominence of juvenile fishes suggests macroalgal meadows facilitate the triphasic life cycle of many fishes occupying diverse tropical seascapes. Correlations between macroalgal canopy structure and juvenile abundance suggests macroalgal habitat condition can influence levels of replenishment in tropical fish populations, including the majority of macroalgal‐associated fishes that are targeted by commercial, subsistence or recreational fisheries. While many macroalgal‐associated fishery species are of minor commercial value, their local importance for food and livelihood security can be substantial (e.g. up to 60% of landings in Kenyan reef fisheries). Given that macroalgal canopy condition can vary substantially with sea temperature, there is a high likelihood that climate change will impact macroalgal‐associated fish and fisheries.

Effects of Saltwater Pulses on Soil Microbial Enzymes and Organic Matter Breakdown in Freshwater and Brackish Coastal Wetlands - Shelby Servais; John S. Kominoski; Carlos Coronado-Molina; Laura Bauman; Stephen E. Davis; Evelyn E. Gaiser; Stephen Kelly; Christopher Madden; Viviana Mazzei; David Rudnik; Fabiola Santamaria; Fred H. Sklar; et al. (Estuaries and Coasts, 2020)

Accumulation characteristics of endosulfan soil residues in soybean and reduction in their phytoavailability by treatment with powdered activated carbon - Jeong-In Hwang; Patrick Christopher Wilson; Jang-Eok Kim (Environmental Science and Pollution Research, 2020)

The Ryanodine Receptor Contributes to the Lysophosphatidylcholine-Induced Mineralization in Valvular Interstitial Cells - Reid L. Wilson; Christopher B. Sylvester; Dena C. Wiltz; Aditya Kumar; Tahir H. Malik; Joel D. Morrisett; K. Jane Grande-Allen (Cardiovascular Engineering and Technology, 2020)

Covariation in superoxide, sperm telomere length and sperm velocity in a polymorphic reptile - Christopher R Friesen; Nicky Rollings; Mark Wilson; Camilla M Whittington; Richard Shine; Mats Olsson (Behavioral Ecology and Sociobiology, 2020)

Experimental Saltwater Intrusion Drives Rapid Soil Elevation and Carbon Loss in Freshwater and Brackish Everglades Marshes - Sean P. Charles; John S. Kominoski; Tiffany G. Troxler; Evelyn E. Gaiser; Shelby Servais; Benjamin J. Wilson; Stephen E. Davis; Fred H. Sklar; Carlos Coronado-Molina; Christopher J. Madden; Steve Kelly; David T. Rudnick (Estuaries and Coasts, 2019)

Beekeeper stewardship, colony loss, and Varroa destructor management - Christopher A. Thoms; Kristen C. Nelson; Andrew Kubas; Nathalie Steinhauer; Michael E. Wilson; Dennis vanEngelsdorp (Ambio, 2019)

Scavenging in the Anthropocene: Human impact drives vertebrate scavenger species richness at a global scale - Esther Sebastián‐González; Jomar Magalhães Barbosa; Juan M. Pérez‐García; Zebensui Morales‐Reyes; Francisco Botella; Pedro P. Olea; Patricia Mateo‐Tomás; Marcos Moleón; Fernando Hiraldo; Eneko Arrondo; José A. Donázar; Ainara Cortés‐Avizanda; et al. (Global Change Biology, 2019)
Understanding the distribution of biodiversity across the Earth is one of the most challenging questions in biology. Much research has been directed at explaining the species latitudinal pattern showing that communities are richer in tropical areas; however, despite decades of research, a general consensus has not yet emerged. In addition, global biodiversity patterns are being rapidly altered by human activities. Here, we aim to describe large‐scale patterns of species richness and diversity in terrestrial vertebrate scavenger (carrion‐consuming) assemblages, which provide key ecosystem functions and services. We used a worldwide dataset comprising 43 sites, where vertebrate scavenger assemblages were identified using 2,485 carcasses monitored between 1991 and 2018. First, we evaluated how scavenger richness (number of species) and diversity (Shannon diversity index) varied among seasons (cold vs. warm, wet vs. dry). Then, we studied the potential effects of human impact and a set of macroecological variables related to climatic conditions on the scavenger assemblages. Vertebrate scavenger richness ranged from species‐poor to species rich assemblages (4–30 species). Both scavenger richness and diversity also showed some seasonal variation. However, in general, climatic variables did not drive latitudinal patterns, as scavenger richness and diversity were not affected by temperature or rainfall. Rainfall seasonality slightly increased the number of species in the community, but its effect was weak. Instead, the human impact index included in our study was the main predictor of scavenger richness. Scavenger assemblages in highly human‐impacted areas sustained the smallest number of scavenger species, suggesting human activity may be overriding other macroecological processes in shaping scavenger communities. Our results highlight the effect of human impact at a global scale. As species‐rich assemblages tend to be more functional, we warn about possible reductions in ecosystem functions and the services provided by scavengers in human‐dominated landscapes in the Anthropocene.

The state of Western Australia’s coral reefs - James P. Gilmour; Kylie L. Cook; Nicole M. Ryan; Marjetta L. Puotinen; Rebecca H. Green; George Shedrawi; Jean-Paul A. Hobbs; Damian P. Thomson; Russell C. Babcock; Joanna Buckee; Taryn Foster; Zoe T. Richards; et al. (Coral Reefs, 2019)

Investigating the predictability of North Atlantic sea surface height - Robert Fraser; Matthew Palmer; Christopher Roberts; Chris Wilson; Dan Copsey; Laure Zanna (Climate Dynamics, 2019)

Atlantic Meridional Overturning Circulation: Observed Transport and Variability - Eleanor Frajka-Williams; Isabelle J. Ansorge; Johanna Baehr; Harry L. Bryden; Maria Paz Chidichimo; Stuart A. Cunningham; Gokhan Danabasoglu; Shenfu Dong; Kathleen A. Donohue; Shane Elipot; Patrick Heimbach; N. Penny Holliday; et al. (Frontiers in Marine Science, 2019)

Crop Water Stress Index of an irrigated vineyard in the Central Valley of California - John H. Prueger; Christopher K. Parry; William P. Kustas; Joseph G. Alfieri; Maria M. Alsina; Héctor Nieto; Tiffany G. Wilson; Lawrence E. Hipps; Martha C. Anderson; Jerry L. Hatfield; Fen Gao; Lynn G. McKee; et al. (Irrigation Science, 2019)

Differential effects of elevation on leaf size of overstorey and understorey species in a temperate rainforest - Steffany A. Nichlos; Clara R. Wilson; Christopher H. Lusk (New Zealand Journal of Botany, 2019)
Conspicuous geographic variation in the average leaf size of plant communities suggests the physical environment must exert strong selection pressures on this trait. Leaf energy balance theory has recently been applied to explain global patterns in leaf size, through its strong influence on vulnerability to (a) overheating in dry sunny conditions and (b) chilling on cold clear nights. The same theory should also predict leaf size patterns on local elevational gradients, but there are fewer data available to examine this prediction. We collected recently‐fallen leaf litter at 50 m elevational intervals in temperate rainforest on Mt. Te Aroha, New Zealand, hypothesising that average leaf size of angiosperm tree and shrub species should decrease with increasing elevation. Data from overstorey species (≥ 10 m tall) strongly supported this hypothesis ( R 2 = 0.36), average leaf size declining from 24.5 cm 2 at 150 m to 4.3 cm 2 at 850 m. Among understorey trees and shrubs ( R 2 = 0.18) and the effect size smaller, average leaf size falling from 29.8 cm 2 at 150 m to 9.8 cm 2 at 850 m. The data are therefore consistent with limitation of leaf size of overstorey species by an elevational decrease in minimum temperatures. Leaf size of shorter tree and shrub species appears to be less constrained by elevational declines in temperature, a pattern that may be partly explained by protection from radiative cooling by overtopping taller trees. However, the occasional occurrence of large‐leaved (notophyll) small trees and shrubs on open, recently‐disturbed sites at high elevation requires clarification.

Predation on oysters is inhibited by intense or chronically mild, low salinity events - Timothy J. Pusack; David L. Kimbro; J. Wilson White; Christopher D. Stallings (Limnology and Oceanography, 2019)
Environmental stress gradients can affect species distributions and interspecific interactions. Because environmental stress depends on both intensity and duration, understanding the consequences of stress requires experiments that simultaneously manipulate both dimensions. In Apalachicola Bay, Florida (U.S.A.) the southern oyster drill ( Stramonita haemastoma ) is a major predator of the eastern oyster ( Crassostrea virginica ). Drill predation appears to be salinity‐dependent: in a recent field study, predation rates were positively correlated with salinity. Salinity in the bay is typically high (> 20) during the dry summer months, conditions that favor both oysters and the drill. However, periodic freshets can dramatically reduce salinity, which inhibits (or kills) drills, but not oysters. In this study, we used field measurements of salinity and drill densities to inform mesocosm experiments. We investigated the specific combinations of intensity and duration of low‐salinity stress that inhibit drill predation. In these experiments, more intense salinity reductions reduced feeding both during and after the low‐salinity stress event. During the event, longer durations (15 d) were necessary for mild salinity reductions (−5) to reduce the feeding rate by the same amount as a short (5 d) exposure of more intense (−10 or −15) salinity reduction. Both conditions may create a predation refuge for oysters, consistent with field observations. Given that the recent collapse of the Apalachicola Bay oyster population was preceded by several years without low‐salinity events to inhibit predation, our results provide a mechanism by which a predator may have contributed to the loss of a historically productive and sustainable fishery.

Long‐term effects of superoxide and DNA repair on lizard telomeres - Mats Olsson; Christopher R. Friesen; Nicky Rollings; Joanna Sudyka; Willow Lindsay; Camilla M. Whittington; Mark Wilson (Molecular Ecology, 2018)
Telomeres are the non‐coding protein‐nucleotide “caps” at chromosome ends that contribute to chromosomal stability by protecting the coding parts of the linear DNA from shortening at cell division, and from erosion by reactive molecules. Recently, there has been some controversy between molecular and cell biologists, on the one hand, and evolutionary ecologists on the other, regarding whether reactive molecules erode telomeres during oxidative stress. Many studies of biochemistry and medicine have verified these relationships in cell culture, but other researchers have failed to find such effects in free‐living vertebrates. Here, we use a novel approach to measure free radicals (superoxide), mitochondrial “content” (a combined measure of mitochondrial number and size in cells), telomere length and DNA damage at two primary time points during the mating season of an annual lizard species ( Ctenophorus pictus ). Superoxide levels early in the mating season vary widely and elevated levels predict shorter telomeres both at that time as well as several months later. These effects are likely driven by mitochondrial content, which significantly impacts late season superoxide (cells with more mitochondria have more superoxide), but superoxide effects on telomeres are counteracted by DNA repair as revealed by 8‐hydroxy‐2′‐deoxyguanosine assays. We conclude that reactive oxygen species and DNA repair are fundamental for both short‐ and long‐term regulation of lizard telomere length with pronounced effects of early season cellular stress detectable on telomere length near lizard death.

An Evaluation of Neurotoxicity Following Fluoride Exposure from Gestational Through Adult Ages in Long-Evans Hooded Rats - Christopher A. McPherson; Guozhu Zhang; Richard Gilliam; Sukhdev S. Brar; Ralph Wilson; Amy Brix; Catherine Picut; G. Jean Harry (Neurotoxicity Research, 2018)

Formulation of High-Performance Dry Powder Aerosols for Pulmonary Protein Delivery - Erin M. Wilson; J. Christopher Luft; Joseph M. DeSimone (Pharmaceutical Research, 2018)

Nitrogen fixation rates diagnosed from diurnal changes in elemental stoichiometry - Christopher L. Follett; Angelicque E. White; Samuel T. Wilson; Michael J. Follows (Limnology and Oceanography, 2018)
The carbon, nitrogen, and phosphorus (C, N, and P, respectively) composition and elemental ratios were measured in the 20–200 μ m size fraction during July 2015 in the surface waters of an anticyclonic eddy encountered north of Hawaii in the oligotrophic North Pacific Subtropical Gyre. The observed particulate N : P ratio fluctuated by approximately a factor of two over the diel cycle. We present a simple mathematical argument connecting this change to a rate of biological nitrogen fixation, and calculate the nitrogen fixation rate to be ≥ 13 nmol L −1 d −1 for this size class. This value is higher than simultaneous bottle‐incubation based rates measured with isotopic tracers, yet is consistent with historic rate measurements from the region. As confirmation of our methods, diurnal changes in C : N : P of laboratory cultures of the diazotrophic genus Trichodesmium were measured. In the laboratory, we show that estimates of nitrogen fixation from stoichiometric time series are equivalent to those derived directly from mass balance. The disparity between nitrogen fixation rates derived from tracer measurements and particulate stoichiometry in the field suggests that large diazotrophs may be underestimated in small volume (∼ 4 L) bottle incubations as a result of either spatial heterogeneity or vertical migration of large cells. Otherwise, processes other than diazotrophy must cause the observed changes in stoichiometry. This approach represents a novel and scalable means of quantifying in situ nitrogen fixation rates from diurnal changes in size‐fractionated stoichiometry. We also infer carbon fixation, growth rates, and phosphorus uptake in the 20–200 μm size class.

Evolution of Melanoma Antigen-A11 (MAGEA11) During Primate Phylogeny - Christopher S. Willett; Elizabeth M. Wilson (Journal of Molecular Evolution, 2018)

Equity trade‐offs in conservation decision making - Elizabeth A. Law; Nathan J. Bennett; Christopher D. Ives; Rachel Friedman; Katrina J. Davis; Carla Archibald; Kerrie A. Wilson (Conservation Biology, 2018)
Conservation decisions increasingly involve multiple environmental and social objectives, which result in complex decision contexts with high potential for trade‐offs. Improving social equity is one such objective that is often considered an enabler of successful outcomes and a virtuous ideal in itself. Despite its idealized importance in conservation policy, social equity is often highly simplified or ill‐defined and is applied uncritically. What constitutes equitable outcomes and processes is highly normative and subject to ethical deliberation. Different ethical frameworks may lead to different conceptions of equity through alternative perspectives of what is good or right. This can lead to different and potentially conflicting equity objectives in practice. We promote a more transparent, nuanced, and pluralistic conceptualization of equity in conservation decision making that particularly recognizes where multidimensional equity objectives may conflict. To help identify and mitigate ethical conflicts and avoid cases of good intentions producing bad outcomes, we encourage a more analytical incorporation of equity into conservation decision making particularly during mechanistic integration of equity objectives. We recommend that in conservation planning motivations and objectives for equity be made explicit within the problem context, methods used to incorporate equity objectives be applied with respect to stated objectives, and, should objectives dictate, evaluation of equity outcomes and adaptation of strategies be employed during policy implementation.

Hummingbirds use taste and touch to discriminate against nectar resources that contain Argentine ants - David T. Rankin; Christopher J. Clark; Erin E. Wilson Rankin (Behavioral Ecology and Sociobiology, 2018)

Development of custom assays for the autonomous detection and quantification of human enteric viruses in seawater using Lab on a Chip - Matthew Wilson; Julie Robidart; Catalin Balan; Christopher Cardwell; Matt Mowlem; Jonathan McQuillan (Frontiers in Marine Science, 2018)

Localised hydrodynamics influence vulnerability of coral communities to environmental disturbances - George Shedrawi; James L. Falter; Kim J. Friedman; Ryan J. Lowe; Morgan S. Pratchett; Christopher J. Simpson; Conrad W. Speed; Shaun K. Wilson; Zhenlin Zhang (Coral Reefs, 2017)

Climatic conditions and nursery habitat quality provide indicators of reef fish recruitment strength - Shaun K. Wilson; Martial Depczynski; Thomas H. Holmes; Mae M. Noble; Ben T. Radford; Paul Tinkler; Christopher J. Fulton (Limnology and Oceanography, 2017)
Identifying and protecting nursery habitats for species is a key conservation strategy for the long‐term sustainability of populations. In tropical ecosystems, macroalgal habitats have recently been identified as nurseries for fish of commercial and conservation significance. Here, we explore how local‐scale variations in seaweed habitat quality interact with large‐scale climatic conditions (Southern Oscillation Index, SOI) to influence the recruitment of three tropical fish species ( Lethrinus spp.), often targeted by fishers. New fish recruits and juveniles of all species were almost exclusively found in macroalgal nursery habitats, while adults of two of these species were predominantly found on adjacent coral reefs. Annual supply rates of new recruits were found to be strongly correlated to variations in the SOI, with La Nina conditions associated with higher recruitment. However, local rates of recruitment were generally poor predictors of older juvenile abundance. Instead, local juvenile abundance was more closely related to structural characteristics of macroalgae nursery habitat quality (density, canopy height, canopy cover) and/or predator biomass, at the time of survey, with species‐specific habitat associations apparent. Given the dynamic nature of fish recruitment supply to the SOI, coupled with the effects of climatic and oceanic processes on the structure of macroalgal patches, these results suggest protection of macroalgal nursery habitats that maintain high canopy density, height and cover is critical to supporting the conservation of fish populations.

Dynamics of direct inter-pack encounters in endangered African wild dogs - Neil R Jordan; Christopher Buse; Alan M Wilson; Krystyna A Golabek; Peter J Apps; John C Lowe; Leanne K Van der Weyde; J Weldon McNutt (Behavioral Ecology and Sociobiology, 2017)

The Andes Cordillera. Part III : glacier surface mass balance and contribution to sea level rise (1979–2014) - Sebastian H. Mernild; Glen E. Liston; Christopher Hiemstra; Ryan Wilson (International Journal of Climatology, 2017)
Glacier surface mass balance ( SMB ) observations for the Andes Cordillera are limited and therefore estimates of the SMB contribution to sea‐level rise are highly uncertain. Here (in Part 3), we simulate glacier surface meteorological and hydrological conditions and trends for the Andes Cordillera (1979/80–2013/14; 35 years), covering the tropical latitudes in the north down to the sub‐polar latitudes in the far south, including the Northern Patagonia Icefield ( NPI ) and Southern Patagonia Icefield ( SPI ). Surface meteorological conditions and heat‐ and mass‐transfer processes were simulated for all glaciers having an area equal to or greater than 0.5 km 2 . SnowModel – a fully integrated energy balance, blowing‐snow distribution, multi‐layer snowpack, and runoff routing model – was used to simulate glacier SMBs for the Andes Cordillera. The Randolph Glacier Inventory ( RGI ; v. 4.0) and NASA Modern‐Era Retrospective Analysis for Research and Applications ( MERRA ) products, downscaled in SnowModel , allowed us to conduct relatively high‐resolution (1‐km horizontal grid; 3‐h time step) simulations of glacier air temperature, precipitation, sublimation, evaporation, runoff, and SMB . These simulated glacier SMBs were verified against both independent direct observed annual glacier SMB and satellite gravimetry and altimetry derived SMB , indicating a good agreement. For Andes glaciers, the 35‐year mean annual SMB was found to be −1.13 m water equivalent (w.e.), while the cumulative SMB was −39.6 m w.e., which is equal to a cumulative SMB contribution of 3.4 mm sea‐level equivalent ( SLE ) (∼0.1 mm SLE per year). However, for both NPI and SPI , the mean SMB was positive (where likely calving explains why geodetic estimates are negative). For the Andes Cordillera, the simulated mean glacier‐specific runoff was 41 L s −1 km −2 , while for NPI and SPI it was 213 and 198 L s −1 km −2 , respectively, indicating available water resources from NPI and SPI .

A global database of nitrogen and phosphorus excretion rates of aquatic animals - Michael J. Vanni; Peter B. McIntyre; Dennis Allen; Diane L. Arnott; Jonathan P. Benstead; David J. Berg; Åge Brabrand; Sébastien Brosse; Paul A. Bukaveckas; Adriano Caliman; Krista A. Capps; Luciana S. Carneiro; et al. (Ecology, 2017)
Animals can be important in modulating ecosystem‐level nutrient cycling, although their importance varies greatly among species and ecosystems. Nutrient cycling rates of individual animals represent valuable data for testing the predictions of important frameworks such as the Metabolic Theory of Ecology ( MTE ) and ecological stoichiometry ( ES ). They also represent an important set of functional traits that may reflect both environmental and phylogenetic influences. Over the past two decades, studies of animal‐mediated nutrient cycling have increased dramatically, especially in aquatic ecosystems. Here we present a global compilation of aquatic animal nutrient excretion rates. The dataset includes 10,534 observations from freshwater and marine animals of N and/or P excretion rates. These observations represent 491 species, including most aquatic phyla. Coverage varies greatly among phyla and other taxonomic levels. The dataset includes information on animal body size, ambient temperature, taxonomic affiliations, and animal body N:P. This data set was used to test predictions of MTE and ES , as described in Vanni and McIntyre (2016; Ecology DOI : 10.1002/ecy.1582 ).

Denial of long‐term issues with agriculture on tropical peatlands will have devastating consequences - Lahiru S. Wijedasa; Jyrki Jauhiainen; Mari Könönen; Maija Lampela; Harri Vasander; Marie‐Claire Leblanc; Stephanie Evers; Thomas E. L. Smith; Catherine M. Yule; Helena Varkkey; Massimo Lupascu; Faizal Parish; et al. (Global Change Biology, 2017)

A test of the migration-modulation hypothesis in a non-passerine Neotropical migrant, the Blue-winged Teal Anas discors - C. Morgan Wilson; Christopher G. Sims; Stephan J. Schoech; Sarah K. Peltier; Zachary L. Robinson (Journal of Ornithology, 2017)

Uses of Innovative Modeling Tools within the Implementation of the Marine Strategy Framework Directive - Christopher P. Lynam; Laura Uusitalo; Joana Patrício; Chiara Piroddi; Ana M. Queirós; Heliana Teixeira; Axel G. Rossberg; Yolanda Sagarminaga; Kieran Hyder; Nathalie Niquil; Christian Möllmann; Christian Wilson; et al. (Frontiers in Marine Science, 2016)

Bridging the Gap between Policy and Science in Assessing the Health Status of Marine Ecosystems - Angel Borja; Michael Elliott; Paul V. R. Snelgrove; Melanie C. Austen; Torsten Berg; Sabine Cochrane; Jacob Carstensen; Roberto Danovaro; Simon Greenstreet; Anna-Stiina Heiskanen; Christopher P. Lynam; Marianna Mea; et al. (Frontiers in Marine Science, 2016)

Identifying the physical features of marina infrastructure associated with the presence of non-native species in the UK - Victoria Foster; Rebecca J. Giesler; A. Meriwether W. Wilson; Christopher R. Nall; Elizabeth J. Cook (Marine Biology, 2016)

Climate‐driven changes to ocean circulation and their inferred impacts on marine dispersal patterns - Laura J. Wilson; Christopher J. Fulton; Andrew McC Hogg; Karen E. Joyce; Ben T. M. Radford; Ceridwen I. Fraser (Global Ecology and Biogeography, 2016)
Aim The dispersal and distribution patterns of many marine organisms are driven by oceanographic conditions, which are influenced by global climate. Climate‐driven oceanographic changes are thus likely to result in biogeographical changes. We assess how recent and predicted oceanographic changes affect the dispersal capacities and distributions of ecologically important (especially habitat‐forming) marine organisms. Location We include studies from tropical, temperate and sub‐polar regions to draw globally relevant conclusions. Methods We review biogeographical, biological and oceanographic studies to critically evaluate emerging trends in biogeographical responses to climate‐driven oceanographic changes, and predict how future changes will affect marine ecosystems. Results Many oceanic dispersal pathways are being altered by climate change. These changes will affect marine ecosystems by differentially affecting the replenishment potential and connectivity of key habitat‐forming species. In particular, the length of propagule pre‐competency periods, propagule behaviour and the geographical distance between areas of suitable habitat will be critical in determining how oceanographic changes affect the pattern and success of dispersal events, including the likelihood of species experiencing poleward range shifts in response to a warming climate. Main conclusions Future climate‐driven oceanographic changes are likely to strengthen or weaken different oceanic dispersal pathways, which will either increase or decrease the potential for dispersal and connectivity in various marine taxa according to the interaction between the local oceanographic, geographical and taxon‐specific biological factors. A key focus for future work should be the development of fine‐scale near‐shore ocean circulation models that can be used to assess the dispersal response of key marine taxa under various marine climate change scenarios.

Genetic diversity of native and introduced populations of the invasive house crow (Corvus splendens) in Asia and Africa - Urszula Krzemińska; Robyn Wilson; Beng Kah Song; Sampath Seneviratne; Sharif Akhteruzzaman; Joanna Gruszczyńska; Wiesław Świderek; Teh Ser Huy; Christopher M. Austin; Sadequr Rahman (Biological Invasions, 2016)

Cognitive activity, cognitive function, and brain diffusion characteristics in old age - Konstantinos Arfanakis; Robert S. Wilson; Christopher M. Barth; Ana W. Capuano; Anil Vasireddi; Shengwei Zhang; Debra A. Fleischman; David A. Bennett (Brain Imaging and Behavior, 2016)

Beta-haemolytic streptococcal endocarditis: clinical presentation, management and outcomes - Abdelghani El Rafei; Daniel C. DeSimone; Christopher V. DeSimone; Brian D. Lahr; James M. Steckelberg; Muhammad R. Sohail; Walter R. Wilson; Larry M. Baddour (Infectious Diseases, 2016)

Short-duration increases in intraluminal pressure improve vasoconstrictor responses in aged skeletal muscle feed arteries - John W. Seawright; Andreea Trache; Emily Wilson; Christopher R. Woodman (European Journal of Applied Physiology, 2016)

Resolving the ancestry of Austronesian-speaking populations - Pedro A. Soares; Jean A. Trejaut; Teresa Rito; Bruno Cavadas; Catherine Hill; Ken Khong Eng; Maru Mormina; Andreia Brandão; Ross M. Fraser; Tse-Yi Wang; Jun-Hun Loo; Christopher Snell; et al. (Human Genetics, 2016)

Evaluation of cystatin C as an early biomarker of cadmium nephrotoxicity in the rat - Walter C. Prozialeck; Aaron VanDreel; Christopher D. Ackerman; Ian Stock; Alexander Papaeliou; Christian Yasmine; Kristen Wilson; Peter C. Lamar; Victoria L. Sears; Joshua Z. Gasiorowski; Karyn M. DiNovo; Vishal S. Vaidya; et al. (BioMetals, 2016)

Genomic sequencing reveals historical, demographic and selective factors associated with the diversification of the fire‐associated fungus Neurospora discreta - Pierre Gladieux; Benjamin A. Wilson; Fanny Perraudeau; Liliam A. Montoya; David Kowbel; Christopher Hann‐Soden; Monika Fischer; Iman Sylvain; David J. Jacobson; John W. Taylor (Molecular Ecology, 2015)
Delineating microbial populations, discovering ecologically relevant phenotypes and identifying migrants, hybrids or admixed individuals have long proved notoriously difficult, thereby limiting our understanding of the evolutionary forces at play during the diversification of microbial species. However, recent advances in sequencing and computational methods have enabled an unbiased approach whereby incipient species and the genetic correlates of speciation can be identified by examining patterns of genomic variation within and between lineages. We present here a population genomic study of a phylogenetic species in the Neurospora discreta species complex, based on the resequencing of full genomes (~37 Mb) for 52 fungal isolates from nine sites in three continents. Population structure analyses revealed two distinct lineages in South–East Asia, and three lineages in North America/Europe with a broad longitudinal and latitudinal range and limited admixture between lineages. Genome scans for selective sweeps and comparisons of the genomic landscapes of diversity and recombination provided no support for a role of selection at linked sites on genomic heterogeneity in levels of divergence between lineages. However, demographic inference indicated that the observed genomic heterogeneity in divergence was generated by varying rates of gene flow between lineages following a period of isolation. Many putative cases of exchange of genetic material between phylogenetically divergent fungal lineages have been discovered, and our work highlights the quantitative importance of genetic exchanges between more closely related taxa to the evolution of fungal genomes. Our study also supports the role of allopatric isolation as a driver of diversification in saprobic microbes.

Embryonic critical windows: changes in incubation temperature alter survival, hatchling phenotype, and cost of development in lake whitefish (Coregonus clupeaformis) - Casey A. Mueller; John Eme; Richard G. Manzon; Christopher M. Somers; Douglas R. Boreham; Joanna Y. Wilson (Journal of Comparative Physiology B, 2015)

Genome-wide association study for refractive astigmatism reveals genetic co-determination with spherical equivalent refractive error: the CREAM consortium - Qing Li; Robert Wojciechowski; Claire L. Simpson; Pirro G. Hysi; Virginie J. M. Verhoeven; Mohammad Kamran Ikram; René Höhn; Veronique Vitart; Alex W. Hewitt; Konrad Oexle; Kari-Matti Mäkelä; Stuart MacGregor; et al. (Human Genetics, 2015)

Paxillin and focal adhesion kinase colocalise in human skeletal muscle and its associated microvasculature - Oliver J. Wilson; Helen Bradley; Christopher S. Shaw; Anton J. M. Wagenmakers (Histochemistry and Cell Biology, 2014)

Corrosion of metal roof materials related to volcanic ash interactions - Christopher Oze; Jim Cole; Allan Scott; Thomas Wilson; Grant Wilson; Sally Gaw; Samuel Hampton; Colin Doyle; Zhengwei Li (Natural Hazards, 2014)

Animating the Carbon Cycle - Oswald J. Schmitz; Peter A. Raymond; James A. Estes; Werner A. Kurz; Gordon W. Holtgrieve; Mark E. Ritchie; Daniel E. Schindler; Amanda C. Spivak; Rod W. Wilson; Mark A. Bradford; Villy Christensen; Linda Deegan; et al. (Ecosystems, 2014)

Sea temperature shapes seasonal fluctuations in seaweed biomass within the Ningaloo coral reef ecosystem - Christopher J. Fulton; Martial. Depczynski; Thomas H. Holmes; Mae M. Noble; Ben Radford; Thomas Wernberg; Shaun K. Wilson (Limnology and Oceanography, 2014)
Environmental drivers of seaweed biomass were investigated at Ningaloo, Western Australia, a coral reef ecosystem with negligible anthropogenic influences on seaweeds from fishing, farming, or eutrophication. Periodic surveys of benthic macroalgae occupying seaweed‐dominated beds within the lagoon at two locations (Coral Bay, Tantabiddi) were made during winter, spring, and late summer over a 26 month period. Canopy‐forming Sargassum spp. biomass fluctuated over a seasonal growth—decay cycle, with highest values in the warm summer months (up to 1013 g fresh weight 0.25 m −2 at Coral Bay) and lowest values in winter (down to 155 g fresh weight 0.25 m −2 at Tantabiddi). Conversely, prominent understory seaweed genera Dictyopteris and Lobophora reached peak biomass in winter, when the Sargassum spp. canopy was lowest. Sargassum spp. biomass variation could be attributed largely to time (52%), location (21%), and site (26%), with low variation within individual seaweed beds (1%). Statistical analysis of the influence of five environmental variables (temperature, light, wind‐driven upwelling, rainfall, significant wave height) indicated that location and sea temperature (1 month antecedent to biomass) provided the best explanation for Sargassum spp. biomass fluctuations. While sea temperature is a key driver of seaweed temporal dynamics, heterogeneity at the kilometer scale suggests that spatial context is also important. Given the important role of seaweeds in many ecosystem processes, this strong biophysical coupling between Sargassum spp. biomass and sea temperature suggests that thermal climate change will significantly affect coral reef productivity and biodiversity.

Multi-species predator eradication within a predator-proof fence at Ka‘ena Point, Hawai‘i - Lindsay C. Young; Eric A. VanderWerf; Michael T. Lohr; Christopher J. Miller; Andrew J. Titmus; Darren Peters; Lindsay Wilson (Biological Invasions, 2013)

Roles of Patch Characteristics, Drought Frequency, and Restoration in Long‐Term Trends of a Widespread Amphibian - BLAKE R. HOSSACK; MICHAEL J. ADAMS; CHRISTOPHER A. PEARL; KRISTINE W. WILSON; EVELYN L. BULL; KRISTIN LOHR; DEBRA PATLA; DAVID S. PILLIOD; JASON M. JONES; KEVIN K. WHEELER; SAMUEL P. MCKAY; PAUL STEPHEN CORN (Conservation Biology, 2013)
Despite the high profile of amphibian declines and the increasing threat of drought and fragmentation to aquatic ecosystems, few studies have examined long‐term rates of change for a single species across a large geographic area. We analyzed growth in annual egg‐mass counts of the Columbia spotted frog ( Rana luteiventris ) across the northwestern United States, an area encompassing 3 genetic clades. On the basis of data collected by multiple partners from 98 water bodies between 1991 and 2011, we used state‐space and linear‐regression models to measure effects of patch characteristics, frequency of summer drought, and wetland restoration on population growth. Abundance increased in the 2 clades with greatest decline history, but declined where populations are considered most secure. Population growth was negatively associated with temporary hydroperiods and landscape modification (measured by the human footprint index), but was similar in modified and natural water bodies. The effect of drought was mediated by the size of the water body: populations in large water bodies maintained positive growth despite drought, whereas drought magnified declines in small water bodies. Rapid growth in restored wetlands in areas of historical population declines provided strong evidence of successful management. Our results highlight the importance of maintaining large areas of habitat and underscore the greater vulnerability of small areas of habitat to environmental stochasticity. Similar long‐term growth rates in modified and natural water bodies and rapid, positive responses to restoration suggest pond construction and other forms of management can effectively increase population growth. These tools are likely to become increasingly important to mitigate effects of increased drought expected from global climate change . Papeles de las Características del Fragmento, Frecuencia de Sequía y Restauración en las Tendencias a Largo Plazo de un Anfibio Ampliamente Distribuido

Effect of age and exercise training on protein:protein interactions among eNOS and its regulatory proteins in rat aortas - Meredith J. Luttrell; John W. Seawright; Emily Wilson; Christopher R. Woodman (European Journal of Applied Physiology, 2013)

Sonic Anemometer as a Small Acoustic Tomography Array - Sergey N. Vecherin; Vladimir E. Ostashev; Christopher W. Fairall; D. Keith Wilson; Ludovic Bariteau (Boundary-Layer Meteorology, 2013)

Myelination and node of Ranvier formation on sensory neurons in a defined in vitro system - John W. Rumsey; Christopher McAleer; Mainak Das; Abhijeet Bhalkikar; Kerry Wilson; Maria Stancescu; Stephen Lambert; James J. Hickman (In Vitro Cellular & Developmental Biology - Animal, 2013)

Impacts of inundation and drought on eukaryote biodiversity in semi‐arid floodplain soils - Darren S. Baldwin; Matthew J. Colloff; Gavin N. Rees; Anthony A. Chariton; Garth O. Watson; Leon N. Court; Diana M. Hartley; Matthew j. Morgan; Andrew J. King; Jessica S. Wilson; Michael Hodda; Christopher M. Hardy (Molecular Ecology, 2013)
Floodplain ecosystems are characterized by alternating wet and dry phases and periodic inundation defines their ecological character. Climate change, river regulation and the construction of levees have substantially altered natural flooding and drying regimes worldwide with uncertain effects on key biotic groups. In southern A ustralia, we hypothesized that soil eukaryotic communities in climate change affected areas of a semi‐arid floodplain would transition towards comprising mainly dry‐soil specialist species with increasing drought severity. Here, we used 18S r RNA amplicon pyrosequencing to measure the eukaryote community composition in soils that had been depleted of water to varying degrees to confirm that reproducible transitional changes occur in eukaryotic biodiversity on this floodplain. Interflood community structures (3 years post‐flood) were dominated by persistent rather than either aquatic or dry‐specialist organisms. Only 2% of taxa were unique to dry locations by 8 years post‐flood, and 10% were restricted to wet locations (inundated a year to 2 weeks post‐flood). Almost half (48%) of the total soil biota were detected in both these environments. The discovery of a large suite of organisms able to survive nearly a decade of drought, and up to a year submerged supports the concept of inherent resilience of Australian semi‐arid floodplain soil communities under increasing pressure from climatic induced changes in water availability.

An acoustic investigation of seagrass photosynthesis - Christopher J. Wilson; Preston S. Wilson; Kenneth H. Dunton (Marine Biology, 2012)

Immunofluorescent visualisation of focal adhesion kinase in human skeletal muscle and its associated microvasculature - Oliver J. Wilson; Christopher S. Shaw; Mark Sherlock; Paul M. Stewart; Anton J. M. Wagenmakers (Histochemistry and Cell Biology, 2012)

Direct evaluation of refractive-index structure functions from large-eddy simulation output for atmospheric convective boundary layers - Christopher Wilson; Evgeni Fedorovich (Acta Geophysica, 2012)

Vulnerability of laptop computers to volcanic ash and gas - Grant Wilson; Thomas Wilson; Jim Cole; Christopher Oze (Natural Hazards, 2012)

Large scale international replication and meta-analysis study confirms association of the 15q14 locus with myopia. The CREAM consortium - Virginie J. M. Verhoeven; Pirro G. Hysi; Seang-Mei Saw; Veronique Vitart; Alireza Mirshahi; Jeremy A. Guggenheim; Mary Frances Cotch; Kenji Yamashiro; Paul N. Baird; David A. Mackey; Robert Wojciechowski; M. Kamran Ikram; et al. (Human Genetics, 2012)

Partitioning fine sediment loads in a headwater system with intensive agriculture - Christopher G. Wilson; A. N. Thanos Papanicolaou; Kevin D. Denn (Journal of Soils and Sediments, 2012)

New constraints on fluid sources in orogenic gold deposits, Victoria, Australia - Bin Fu; Mark A. Kendrick; Alison M. Fairmaid; David Phillips; Christopher J. L. Wilson; Terrence P. Mernagh (Contributions to Mineralogy and Petrology, 2012)

Erratum to:Dengue virus-specific CD4+ and CD8+ T lymphocytes target NS1, NS3 and NS5 in infected Indian rhesus macaques - Katherine M. Mladinich; Shari M. Piaskowski; Richard Rudersdorf; Christopher M. Eernisse; Kim L. Weisgrau; Mauricio A. Martins; Jessica R. Furlott; Charalambos D. Partidos; Joseph N. Brewoo; Jorge E. Osorio; Nancy A. Wilson; Eva G. Rakasz; et al. (Immunogenetics, 2012)

Flux by fin: fish-mediated carbon and nutrient flux in the northeastern Gulf of Mexico - James Nelson; Rachel Wilson; Felicia Coleman; Christopher Koenig; Doug DeVries; Chris Gardner; Jeff Chanton (Marine Biology, 2012)

Dengue virus-specific CD4+ and CD8+ T lymphocytes target NS1, NS3 and NS5 in infected Indian rhesus macaques - Katherine M. Mladinich; Shari M. Piaskowski; Richard Rudersdorf; Christopher M. Eernisse; Kim L. Weisgrau; Mauricio A. Martins; Jessica R. Furlott; Charalambos D. Partidos; Joseph N. Brewoo; Jorge E. Osorio; Nancy A. Wilson; Eva G. Rakasz; et al. (Immunogenetics, 2012)

Marine dispersal as a pre‐requisite for Gondwanan vicariance among elements of the galaxiid fish fauna - Christopher P. Burridge; Robert M. McDowall; Dave Craw; Mark V. H. Wilson; Jonathan M. Waters (Journal of Biogeography, 2012)
Aim The aim of this study was to determine the contributions of Gondwanan vicariance and marine dispersal to the contemporary distribution of galaxiid fishes. This group has been central in arguments concerning the roles of dispersal and vicariance in the Southern Hemisphere, as some taxa have marine life history stages through which transoceanic dispersal may have been facilitated, yet other galaxiids are entirely restricted to freshwaters. Location Southern Hemisphere land masses of Gondwanan derivation. Methods Biogeographic hypotheses of Gondwanan vicariance and marine dispersal were tested using four lines of evidence: (1) concordance of species–area phylogenetic relationships, (2) molecular estimates of lineage divergence times with a priori expectations based on plate tectonics, (3) reconstructions of ancestral dispersal capabilities, and (4) reconstructions of distribution inheritance scenarios (using the dispersal–extinction–cladogenesis model to infer historical ranges and dispersal and extinction events). Results Phylogenetic relationships were reconstructed from 4531 mitochondrial and nuclear nucleotide characters, and 181 morphological characters, across 53 of the 56 presently recognized species. Phylogenetic relationships were generally well resolved and supported among galaxiids using the combined dataset, and conflicting relationships between molecular and morphological datasets typically received low topological support from either or both datasets. Transoceanic disjunctions were exhibited at 16 nodes, but only three pre‐dated relevant continental fragmentation events; furthermore, ancestral distribution inheritance scenarios for two of these nodes reflected cladogenesis within, rather than between, Gondwanan land masses, and ancestral marine dispersal capability could not be rejected for all three. Instead, the four lines of evidence surveyed suggest that Gondwanan vicariance occurred twice, but in both instances was preceded by marine dispersal between land masses, and in at least one instance was initiated by the cessation of marine dispersal subsequent to continental fragmentation. Main conclusions Gondwanan vicariance appears to have been preceded by marine dispersal in the few instances where it may explain contemporary galaxiid distribution, such that these biogeographic mechanisms may sometimes have a synergistic relationship.

Human Dimensions / Recreation and Ecotourism - Rachel Billingham; Marissa Jo Daniel; Francisco Aguilar; Hank Stelzer; Guy Robertson; Stanley Asah; Michelle King; Angela Gupta; Samatha Grant; Christopher Jones; Melanie Lenart; Richard Tholen; et al. (Journal of Forestry, 2011)
8With the current state of the economy and the budget woes found in everyone's workplace, every extra dollar we can use to offset the cost of projects counts—and what if those extra dollars came with public relations opportunities at no cost to you? For the last several years, the Pennsylvania Bureau of Forestry has cultivated relationships with a variety of non-traditional partners. These relationships have not only provided additional funds for tree planting projects through our TreeVitalize program, but have also provided fantastic public relations exposure and access to new audiences. Come hear how we used a “win-win” approach with our new partners and be inspired to try some of these ideas in your “neck of the woods.”

The role of MHC class I allele Mamu-A*07 during SIVmac239 infection - Jason S. Reed; John Sidney; Shari M. Piaskowski; Chrystal E. Glidden; Enrique J. León; Benjamin J. Burwitz; Holly L. Kolar; Christopher M. Eernisse; Jessica R. Furlott; Nicholas J. Maness; Andrew D. Walsh; Richard A. Rudersdorf; et al. (Immunogenetics, 2011)

Gene transfer provides a practical means for safe, long-term, targeted delivery of biologically active neurotrophic factor proteins for neurodegenerative diseases - Christopher D. Herzog; Kathie M. Bishop; Lamar Brown; Alistair Wilson; Jeffrey H. Kordower; Raymond T. Bartus (Drug Delivery and Translational Research, 2011)

Baseline Ecological Risk Assessment of the Calcasieu Estuary, Louisiana: Part 1. Overview and Problem Formulation - Donald D. MacDonald; Dwayne R. J. Moore; Christopher G. Ingersoll; Dawn E. Smorong; R. Scott Carr; Ron Gouguet; David Charters; Duane Wilson; Tom Harris; Jon Rauscher; Susan Roddy; John Meyer (Archives of Environmental Contamination and Toxicology, 2011)

Joint effects of germ-line TP53 mutation, MDM2 SNP309, and gender on cancer risk in family studies of Li–Fraumeni syndrome - Chih-Chieh Wu; Ralf Krahe; Guillermina Lozano; Baili Zhang; Charmaine D. Wilson; Eun-Ji Jo; Christopher I. Amos; Sanjay Shete; Louise C. Strong (Human Genetics, 2011)

Structural and kinetic studies of imidazole binding to two members of the cytochrome c 6 family reveal an important role for a conserved heme pocket residue - Badri S. Rajagopal; Michael T. Wilson; Derek S. Bendall; Christopher J. Howe; Jonathan A. R. Worrall (JBIC Journal of Biological Inorganic Chemistry, 2011)

Genetic association analysis highlights new loci that modulate hematological trait variation in Caucasians and African Americans - Ken Sin Lo; James G. Wilson; Leslie A. Lange; Aaron R. Folsom; Geneviève Galarneau; Santhi K. Ganesh; Struan F. A. Grant; Brendan J. Keating; Steven A. McCarroll; Emile R. Mohler III; Christopher J. O’Donnell; Walter Palmas; et al. (Human Genetics, 2011)

Estimation of late twentieth century land-cover change in California - Benjamin M. Sleeter; Tamara S. Wilson; Christopher E. Soulard; Jinxun Liu (Environmental Monitoring and Assessment, 2011)

Novel Approach for Endothelializing Vascular Devices: Understanding and Exploiting Elastin–Endothelial Interactions - Brent D. Wilson; Christopher C. Gibson; Lise K. Sorensen; Margaret Yoklavich Guilhermier; Melissa Clinger; Linda L. Kelley; Yan-Ting E. Shiu; Dean Y. Li (Annals of Biomedical Engineering, 2011)

Obesogenic high fat western diet induces oxidative stress and apoptosis in rat heart - Kalpana Ballal; Christopher R. Wilson; Romain Harmancey; Heinrich Taegtmeyer (Molecular and Cellular Biochemistry, 2010)

The live-attenuated yellow fever vaccine 17D induces broad and potent T cell responses against several viral proteins in Indian rhesus macaques—implications for recombinant vaccine design - Philip A. Mudd; Shari M. Piaskowski; Patricia C. Costa Neves; Richard Rudersdorf; Holly L. Kolar; Christopher M. Eernisse; Kim L. Weisgrau; Marlon G. Veloso de Santana; Nancy A. Wilson; Myrna C. Bonaldo; Ricardo Galler; Eva G. Rakasz; et al. (Immunogenetics, 2010)

Visfatin induces oxidative stress in differentiated C2C12 myotubes in an Akt- and MAPK-independent, NFĸB-dependent manner - Radu C. Oita; Dudley Ferdinando; Steve Wilson; Christopher Bunce; Dawn J. Mazzatti (Pflügers Archiv - European Journal of Physiology, 2010)

Comparative genomics based on massive parallel transcriptome sequencing reveals patterns of substitution and selection across 10 bird species - AXEL KÜNSTNER; JOCHEN B. W. WOLF; NICLAS BACKSTRÖM; OSCEOLA WHITNEY; CHRISTOPHER N. BALAKRISHNAN; LAINY DAY; SCOTT V. EDWARDS; DANIEL E. JANES; BARNEY A. SCHLINGER; RICHARD K. WILSON; ERICH D. JARVIS; WESLEY C. WARREN; et al. (Molecular Ecology, 2010)
Next‐generation sequencing technology provides an attractive means to obtain large‐scale sequence data necessary for comparative genomic analysis. To analyse the patterns of mutation rate variation and selection intensity across the avian genome, we performed brain transcriptome sequencing using Roche 454 technology of 10 different non‐model avian species. Contigs from de novo assemblies were aligned to the two available avian reference genomes, chicken and zebra finch. In total, we identified 6499 different genes across all 10 species, with ∼1000 genes found in each full run per species. We found evidence for a higher mutation rate of the Z chromosome than of autosomes (male‐biased mutation) and a negative correlation between the neutral substitution rate ( d S ) and chromosome size. Analyses of the mean d N / d S ratio (ω) of genes across chromosomes supported the Hill–Robertson effect (the effect of selection at linked loci) and point at stochastic problems with ω as an independent measure of selection. Overall, this study demonstrates the usefulness of next‐generation sequencing for obtaining genomic resources for comparative genomic analysis of non‐model organisms.

Carbonate spots: understanding the relationship to gold mineralization in Central Victoria, southeastern Australia - Allison L. Dugdale; Christopher J. L. Wilson; Lawrence D. Leader; Jamie A. Robinson; L. Jonathon Dugdale (Mineralium Deposita, 2009)

Methods for Quantifying Three-Dimensional Deformation of Arteries due to Pulsatile and Nonpulsatile Forces: Implications for the Design of Stents and Stent Grafts - Gilwoo Choi; Christopher P. Cheng; Nathan M. Wilson; Charles A. Taylor (Annals of Biomedical Engineering, 2009)

Initial nicotine sensitivity in humans as a function of impulsivity - Kenneth A. Perkins; Caryn Lerman; Sarah B. Coddington; Christopher Jetton; Joshua L. Karelitz; John A. Scott; Annette S. Wilson (Psychopharmacology, 2008)

The upscaling of transpiration from individual trees to areal transpiration in tree belts - Russell S. Crosbie; Brett Wilson; Justin D. Hughes; Christopher McCulloch (Plant and Soil, 2008)

Aureoles of Pb(II)-enriched feldspar around monazite in paragneiss and anatectic pods of the Napier Complex, Enderby Land, East Antarctica: the roles of dissolution-reprecipitation and diffusion - Edward S. Grew; Martin G. Yates; Christopher J. L. Wilson (Contributions to Mineralogy and Petrology, 2008)

Low Dose Lipid Formulations: Effects on Gastric Emptying and Biliary Secretion - Greg A. Kossena; William N. Charman; Clive G. Wilson; Bridget O’Mahony; Blythe Lindsay; John M. Hempenstall; Christopher L. Davison; Patrick J. Crowley; Christopher J. H. Porter (Pharmaceutical Research, 2007)

The upscaling of transpiration from individual trees to areal transpiration in tree belts - Russell S. Crosbie; Brett Wilson; Justin D. Hughes; Christopher McCulloch (Plant and Soil, 2007)

Removal of ocular artifacts from the EEG: a comparison between time-domain regression method and adaptive filtering method using simulated data - Ping He; Glenn Wilson; Christopher Russell; Maria Gerschutz (Medical & Biological Engineering & Computing, 2007)

The use of7Be and210Pbxs to differentiate fine suspended sediment sources in South Slough, Oregon - Christopher G. Wilson; Gerald Matisoff; Peter J. Whiting (Estuaries and Coasts, 2007)

Effect of ocean conditions on the cross‐shelf distribution of walleye pollock ( Theragra chalcogramma ) and capelin ( Mallotus villosus ) - ANNE BABCOCK HOLLOWED; CHRISTOPHER D. WILSON; PHYLLIS J. STABENO; SIGRID A. SALO (Fisheries Oceanography, 2007)
Acoustic trawl surveys were conducted in 2000 and 2001 in two troughs located off the eastern coast of Kodiak Island in the Gulf of Alaska as part of a multiyear, multidisciplinary experiment to examine the influence of environmental conditions on the spatial distribution of adult and juvenile walleye pollock ( Theragra chalcogramma ) and capelin ( Mallotus villosus ). Continuous underway sea surface temperature samples and water column profiles collected in 2000 and 2001 showed the presence of a sharp shelf‐break front in Chiniak Trough and a mid‐trough front in Barnabas Trough. At distances a to the surface and enhanced nutrients in the surface waters. The storm event revealed spatial partitioning of summer production in Barnabas Trough, with production concentrated in regions inside the mid‐trough front. In contrast, post‐storm summer production was distributed throughout Chiniak Trough. The spatial distribution of walleye pollock and capelin differed and appeared to be related to differences in habitat characteristics. Acoustic survey data identified four acoustic sign types: age‐1 pollock, adult pollock, capelin, capelin–age‐0 pollock mix. The spatial distribution of these four sign types appears to be influenced by the oceanographic and topographic features of the two troughs. Adult pollock were broadly distributed throughout Chiniak Trough, whereas adult pollock were aggregated on the coastal side of the frontal system in Barnabas Trough. In 2000, capelin occurred with age‐0 pollock. In Chiniak Trough, capelin were most abundant along steep topographic gradients at the edges of the trough and in a deep region near Cape Chiniak, whereas the capelin–age‐0 mix (2000) or capelin (2001) concentrations were observed in slope water intrusions over the outer shelf in Barnabas Trough. Results suggest that habitat selection of walleye pollock and capelin are controlled by different processes. Capelin distributions appear to be limited by oceanographic conditions while other factors appear to be more important for pollock.

Two-locus genome-wide linkage scan for prostate cancer susceptibility genes with an interaction effect - Bao-Li Chang; Ethan M. Lange; Latchezar Dimitrov; Christopher J. Valis; Elizabeth M. Gillanders; Leslie A. Lange; Kathleen E. Wiley; Sarah D. Isaacs; Fredrik Wiklund; Agnes Baffoe-Bonnie; Carl D Langefeld; S. Lilly Zheng; et al. (Human Genetics, 2006)

Development and Characterization of a Scalable Controlled Precipitation Process to Enhance the Dissolution of Poorly Water-Soluble Drugs - True L. Rogers; Ian B. Gillespie; James E. Hitt; Kevin L. Fransen; Cindy A. Crowl; Christopher J. Tucker; Gary B. Kupperblatt; Joe N. Becker; Deb L. Wilson; Clifford Todd; Charles F. Broomall; Jonathan C. Evans; et al. (Pharmaceutical Research, 2004)

Time series analysis of elemental and isotopic data from biomineralized whale tissue - Qin Shao; Machelle D. Wilson; Christopher S. Romanek; Keith A. Hobson (Environmental and Ecological Statistics, 2004)

Calcitonin gene-related peptide is not essential for the development of pressure overload-induced hypertrophy in vivo - Martin E. Young; Kristen A. Okerberg; Christopher R. Wilson; Dario A. Deferrari; Jun Ying; Patrick Guthrie; Peter Razeghi; Fred J. Clubb; Heinrich Taegtmeyer (Molecular and Cellular Biochemistry, 2001)

Ultrasound for the Visualization and Quantification of Tumor Microcirculation - F. Stuart Foster; Peter N. Burns; David H. Simpson; Stephanie R. Wilson; Donald A. Christopher; David E. Goertz (Cancer and Metastasis Reviews, 2000)

Use of a conceptual model of societal drivers of ecological change in South Florida: Implications of an ecosystem management scenario - Christine C. Harwell; Christopher W. Deren; George H. Snyder; William D. Solecki; James Wilson; Mark A. Harwell (Urban Ecosystems, 1999)

Comparative phylogeography of Nearctic and Palearctic fishes - LOUIS BERNATCHEZ; CHRISTOPHER C. WILSON (Molecular Ecology, 1998)
Combining phylogeographic data from mitochondrial DNA (mtDNA) of Nearctic and Palearctic freshwater and anadromous fishes, we used a comparative approach to assess the influence of historical events on evolutionary patterns and processes in regional fish faunas. Specifically, we (i) determined whether regional faunas differentially affected by Pleistocene glaciations show predictable differences in phylogeographic patterns; (ii) evaluated how processes of divergence and speciation have been influenced by such differential responses; and (iii) assessed the general contribution of phylogeographic studies to conservation issues. Comparisons among case studies revealed fundamental differences in phylogeographic patterns among regional faunas. Tree topologies were typically deeper for species from nonglaciated regions compared to northern species, whereas species with partially glaciated ranges were intermediate in their characteristics. Phylogeographic patterns were strikingly similar among southern species, whereas species in glaciated areas showed reduced concordance. The extent and locations of secondary contact among mtDNA lineages varied greatly among northern species, resulting in reduced intraspecific concordance of genetic markers for some northern species. Regression analysis of phylogeographic data for 42 species revealed significant latitudinal shifts in intraspecific genetic diversity. Both relative nucleotide diversity and estimates of evolutionary effective population size showed significant breakpoints matching the median latitude for the southern limit of the Pleistocene glaciations. Similarly, analysis of clade depth of phylogenetically distinct lineages vs. area occupied showed that evolutionary dispersal rates of species from glaciated and nonglaciated regions differed by two orders of magnitude. A negative relationship was also found between sequence divergence among sister species as a function of their median distributional latitude, indicating that recent bursts of speciation events have occurred in deglaciated habitats. Phylogeographic evidence for parallel evolution of sympatric northern species pairs in postglacial times suggested that differentiation of cospecific morphotypes may be driven by ecological release. Altogether, these results demonstrate that comparative phylogeography can be used to evaluate not only phylogeographic patterns but also evolutionary processes. As well as having significant implications for conservation programs, this approach enables new avenues of research for examining the regional, historical, and ecological factors involved in shaping intraspecific genetic diversity.

Planning for the Inaugural Meeting of The Oceanography Society - Stanley Wilson; Christopher Mooers (Oceanography, 1988)

Age changes in geometry and mineral content of the lower limb bones - Christopher B. Ruff; Wilson C. Hayes (Annals of Biomedical Engineering, 1984)